1,10]Phenanthroline based cyanine dyes as fluorescent probes for ribonucleic acids in live cells - Kovalska, Vladyslava B.; Kuperman, Marina; Varzatskii, Oleg; Kryvorotenko, Dmytro; Kinski, Elisa; Schikora, Margot; Janko, Christina; Alexiou, Christoph; Yarmoluk, Sergiy; Mokhir, Andriy (Methods and Applications in Fluorescence, 2017)
A series of monomethine, trimethine- and styrylcyanine dyes based on a [1,10]phenanthroline moiety was synthesized, characterized and investigated as potential fluorescent probes for nucleic acids in cell free settings and in cells. The dyes were found to be weakly fluorescent in the unbound state, whereas upon the binding to dsDNA or RNA their emission intensity raised up to 50 times (for monomethine benzothiazole derivative FT1 complexed with RNA). The strongest fluorescence intensity in assemblies with dsDNA and RNA was observed for the trimethine benzothiazole derivative FT4. The quantum yield of FT4 fluorescence in its complex with dsDNA was found to be 1.5% and the binding constant (K b) was estimated to be 7.9 × 104 M-1 that is a typical value for intercalating molecules. The FT4 dye was found to be cell membrane permeable. It stains RNA rich components-the nucleoli and most probably the cytoplasmic RNA. FT4 bound to RNAs delivers a very strong fluorescence signal, which makes this easily accessible dye a potentially useful alternative to known RNA stains, e.g. expensive SYTO® 83. The advantage of FT4 is its easy synthetic access including no chromatographic purification steps, which will be reflected in its substantially lower price.
EVALuna2:35777

1,9-dialkoxyanthracene as a 1O 2-sensitive linker - Arian, Dumitru; Kovbasyuk, Larisa; Mokhir, Andriy (Journal of the American Chemical Society, 2011)
We developed a O -sensitive linker based on a 9,10-dialkoxyanthracene structure. Its cleavage in the presence of O is quick and high-yielding. A phosphoramidite containing this fragment was prepared and coupled to a variety of molecular fragments, including nucleosides, fluorescent dyes, and a cholesteryl derivative. On the basis of this building block we prepared a fluorogenic probe for monitoring O in live mammalian cells and visible-light-activated "caged" oligodeoxyribonucleotides. In particular, the fluorogenic O probe is a conjugate of 4,7,4′,7′-tetrachlorofluorescein and N,N,N′,N′- tetramethylrhodamine coupled to each other via the O -sensitive linker. Fluorescence of the dyes in this probe is quenched. In the presence of O , the linker is cleaved with formation of 9,10-anthraquinone and two strongly fluorescent dyes: 4,7,4′,7′-tetrachlorofluorescein and N,N,N′,N′- tetramethylrhodamine derivatives. We observed that the fluorescence of the probe correlates with the amount of O present in solution. The red-light-activated "caged" oligodeoxyribonucleotides are stable duplexes, which consist of an unmodified strand and a blocker strand. The O -sensitive linker is introduced in the interior of the blocker strand. Upon exposure of the duplex to red light in the presence of In (pyropheophorbide-a) chloride, the linker is cleaved with formation of the unstable duplex structure. This product decomposes spontaneously, releasing the unmodified strand, which can bind to the complementary target nucleic acid. This uncaging reaction is high-yielding. In contrast, previously reported visible-light-activated reagents are uncaged inefficiently due to competing reactions of sulfoxide and disulfide formation. © 2011 American Chemical Society.

3D-Shaped Binders of Unfolded Proteins Inducing Cancer Cell-Specific Endoplasmic Reticulum Stress In Vitro and In Vivo - Klemt, Insa; Varzatskii, Oleg; Selin, Roman; Vakarov, Serhii; Kovalska, Vladyslava B.; Bila, Galyna; Bilyy, Rostyslav; Voloshin, Yan; Cossío Cuartero, Itziar; Hidalgo, Andrés; Frey, Benjamin; Becker, Ina; et al. (Journal of the American Chemical Society, 2023)
The amount of unfolded proteins is increased in cancer cells, leading to endoplasmic reticulum (ER) stress. Therefore, cancer cells are sensitive to drugs capable of further enhancing ER stress. Examples of such drugs include the clinically approved proteosome inhibitors bortezomib and carfilzomib. Unfortunately, the known ER stress inducers exhibit dose-limiting side effects that justify the search for better, more cancer-specific drugs of this type. Herein, we report on FeC 2, which binds to unfolded proteins prevents their further processing, thereby leading to ER stress and ROS increase in cancer cells, but not in normal cells. FeC 2 exhibits low micromolar toxicity toward human acute promyelocytic leukemia HL-60, Burkitt’s lymphoma BL-2, T-cell leukemia Jurkat, ovarian carcinoma A2780, lung cancer SK-MES-1, and murine lung cancer LLC1 cells. Due to the cancer-specific mode of action, 2 is not toxic in vivo up to the dose of 147 mg/kg, does not affect normal blood and bone marrow cells at the therapeutically active dose, but strongly suppresses both primary tumor growth (confirmed in Nemeth-Kellner lymphoma and LLC1 lung cancer models of murine tumor) and spreading of metastases (LLC1).

4-Azidobenzyl ferrocenylcarbamate as an anticancer prodrug activated under reductive conditions - Kinski, Elisa; Marzenell, Paul; Hofer, Walter; Hagen, Helen; Raskatov, Jevgenij A.; Knaup, Karl; Zolnhofer, Eva; Meyer, Karsten; Mokhir, Andriy (Journal of Inorganic Biochemistry, 2016)
Aminoferrocene-based prodrugs are activated in the presence of cancer-specific amounts of reactive oxygen species, e.g. H2O2, with the formation of products of two types: Fe-containing complexes, which catalyze generation of HO and O2-, and quinone methides, which alkylate glutathione and inhibit the antioxidative system of the cell. Both processes act synergistically by increasing the oxidative stress in cancer cells thereby leading to their death. However, in the activation step including the cleavage of a B-C bond one molecule of H2O2 is consumed that counteracts the desired effect of the products released from aminoferrocenes. We replaced an H2O2-sensitive trigger in original prodrugs with an azide group. This trigger is slowly reduced in the presence of glutathione with the formation of an unstable arylamine intermediate, which decomposes with the release of iron ions and iminoquinone methides. These products induce strong oxidative stress in cells as we confirmed using 2′,7′-dichlorodihydrofluorescin diacetate reagent in combination with flow cytometry. In this case the activation process does not consume H2O2. Correspondingly, we observed that the azide-containing prodrug is substantially more toxic towards human promyelocytic leukemia cell line HL-60 (IC50 = 27 ± 4 μM) than its H2O2-responsive analogue (IC50 > 50 μM).
CRIS-Team Scopus Importer:2020-09-14
Keywords: Azide; Cancer; Ferrocene; Prodrug; Reduction

4-Ferrocenylaniline-based ROS-responsive prodrugs with anticancer activity - Xu, Honggui; Annamadov, Saparmyrat; Mokhir, Andriy (Journal of Organometallic Chemistry, 2022)
Ferrocene derivatives often exhibit anticancer activity. For example, our group has developed aminoferrocene-based (AF) prodrugs, which are activated in the presence of reactive oxygen species (ROS), present in large quantities in cancer cells. The activation reaction leads to formation of AF's, whose redox potential is shifted by 300–400 mV to negative values as compared to the parent AF prodrugs. Correspondingly, these drugs are very electron rich and can, therefore, act as catalysts of generation of highly toxic hydroxyl radicals (HO●) from H2O2. That contributes to the cytotoxicity of AF prodrugs. Unfortunately, AF's are chemically very unstable. Therefore, their lifetime in cells is < 1 h that limits the anticancer activity of the AF prodrugs. In this paper we report on new 4-ferrocenylaniline-based (4-FcAn) prodrugs. These are activated in the presence of ROS thereby releasing 4-FcAn. We confirmed that 4-FcAn is more electron rich than the corresponding prodrug (ΔE1/2 = 86 mV) and can generate HO● from H2O2 analogously to AF. Furthermore, we observed that (a) 4-ferrocenylanilines are substantially more stable (>6 h) than AF's and (b) the corresponding prodrugs are substantially more active than the structurally related AF prodrugs. We found that, analogously to AF prodrugs, the new prodrugs exhibit their anticancer activity via generation of ROS in cancer cells.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Anticancer; Ferrocene; Prodrug; Reactive oxygen species; Redox catalysis

A concept of dual-responsive prodrugs based on oligomerization-controlled reactivity of ester groups: an improvement of cancer cells versus neutrophils selectivity of camptothecin - Klemt, Insa; Reshetnikov, Viktor; Dutta, Subrata; Bila, Galyna; Bilyy, Rostyslav; Cuartero, Itziar Cossío; Hidalgo, Andrés; Wünsche, Adrian; Böhm, Maximilian; Wondrak, Marit; Kunz-Schughart, Leoni A.; Tietze, Rainer; et al. (RSC Medicinal Chemistry, 2024)
Many known chemotherapeutic anticancer agents exhibit neutropenia as a dose-limiting side effect. In this paper we suggest a prodrug concept solving this problem for camptothecin (HO-cpt). The prodrug is programmed according to Boolean “AND” logic. In the absence of H2O2 (trigger T1), e.g. in the majority of normal cells, it exists as an inactive oligomer. In cancer cells and in primed neutrophils (high H2O2), the oligomer is disrupted forming intermediate (inactive) lipophilic cationic species. These are accumulated in mitochondria (Mit) of cancer cells, where they are activated by hydrolysis at mitochondrial pH 8 (trigger T2) with formation of camptothecin. In contrast, the intermediates remain stable in neutrophils lacking Mit and therefore a source of T2. In this paper we demonstrated a proof-of-concept. Our prodrug exhibits antitumor activity both in vitro and in vivo, but is not toxic to normal cell and neutrophils in contrast to known single trigger prodrugs and the parent drug HO-cpt.
CRIS-Team Scopus Importer:2024-04-19

Aminoferrocene-Based Anticancer Prodrugs Labelled with Cyanine Dyes for in vivo Imaging - Özkan, Hülya; Toms, Johannes; Maschauer, Simone; Prante, Olaf; Mokhir, Andriy (European Journal of Inorganic Chemistry, 2021)
N-alkylaminoferrocene-based (NAAF) prodrugs are activated in the presence of reactive oxygen species (ROS), based on which these prodrugs target cancer cells (high ROS) and do not affect normal cells (low ROS). To gain some insights into their mode of action in vivo, we have investigated the biodistribution of 18F-labelled NAAF prodrugs in tumor-bearing mice by positron emission tomography (PET). Due to the short half-life of 18F, the experimental time frame was restricted to 60 min. To extend the observation window, a more stable marker is required. In this paper, we report on conjugates of NAAF prodrugs with two cyanine dyes Cy5 and Cy7 including details of their synthesis, characterization and basic properties in cell free settings and their cellular uptake in representative human cancer cells. Finally, the Cy5 conjugate was subjected to in vivo fluorescence imaging studies to determine the prodrug biodistribution over 24 h.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Anticancer; Ferrocene; Imaging; Prodrug; Reactive oxygen species

Aminoferrocene-based prodrugs activated by reactive oxygen species - Hagen, Helen; Marzenell, Paul; Jentzsch, Elmar; Wenz, Frederik; Veldwijk, Marlon R.; Mokhir, Andriy (Journal of Medicinal Chemistry, 2012)
Cancer cells generally generate higher amounts of reactive oxygen species than normal cells. On the basis of this difference, prodrugs have been developed (e.g., hydroxyferrocifen), which remain inactive in normal cells, but become activated in cancer cells. In this work we describe novel aminoferrocene-based prodrugs, which, in contrast to hydroxyferrocifen, after activation form not only quinone methides (QMs), but also catalysts (iron or ferrocenium ions). The released products act in a concerted fashion. In particular, QMs alkylate glutathione, thereby inhibiting the antioxidative system of the cell, whereas the iron species induce catalytic generation of hydroxyl radicals. Since the catalysts are formed as products of the activation reaction, it proceeds autocatalytically. The most potent prodrug described here is toxic toward cancer cells (human promyelocytic leukemia (HL-60), IC = 9 μM, and human glioblastoma-astrocytoma (U373), IC = 25 μM), but not toxic (up to 100 μM) toward representative nonmalignant cells (fibroblasts). © 2011 American Chemical Society.

Aminoferrocene-based prodrugs and their effects on human normal and cancer cells as well as bacterial cells - Marzenell, Paul; Hagen, Helen; Sellner, Leopold; Zenz, Thorsten; Grinyte, Ruta; Pavlov, Valeri; Daum, Steffen; Mokhir, Andriy (Journal of Medicinal Chemistry, 2013)
Aminoferrocene-based prodrugs are activated under cancer-specific conditions (high concentration of reactive oxygen species, ROS) with the formation of glutathione scavengers (p-quinone methide) and ROS-generating iron complexes. Herein, we explored three structural modifications of these prodrugs in an attempt to improve their properties: (a) the attachment of a -COOH function to the ferrocene fragment leads to the improvement of water solubility and reactivity in vitro but also decreases cell-membrane permeability and biological activity, (b) the alkylation of the N-benzyl residue does not show any significant affect, and (c) the attachment of the second arylboronic acid fragment improves the toxicity (IC) of the prodrugs toward human promyelocytic leukemia cells (HL-60) from 52 to 12 μM. Finally, we demonstrated that the prodrugs are active against primary chronic lymphocytic leukemia (CLL) cells, with the best compounds exhibiting an IC value of 1.5 μM. The most active compounds were found to not affect mononuclear cells and representative bacterial cells. © 2013 American Chemical Society.

Amplification of net formation induces resolution of inflammation - Euler, Maximilien; Hahn, Jonas; Herrmann, Martin; Mokhir, Andriy; Hoffmann, Markus (FREE RADICAL BIOLOGY AND MEDICINE, 2019)
CRIS-Team WoS Importer:2019-06-28

An autocatalytic chromogenic and fluorogenic photochemical reaction controlled by nucleic acids - Dutta, Subrata; Mokhir, Andriy (Chemical Communications, 2011)
The autocatalytic photochemical reaction, which is potentially controlled by any selected nucleic acid, is highly sequence specific and not inhibited by its products, was developed. This reaction generates colored and fluorescent products, which can be monitored by the naked eye. © 2011 The Royal Society of Chemistry.

An Endoplasmic Reticulum Specific Pro-amplifier of Reactive Oxygen Species in Cancer Cells - Xu, Honggui; Schikora, Margot; Sisa, Miroslav; Daum, Steffen; Klemt, Insa; Janko, Christina; Alexiou, Christoph; Bila, Galyna; Bilyy, Rostyslav; Gong, Wenjie; Schmitt, Michael; Sellner, Leopold; et al. (Angewandte Chemie International Edition, 2021)
The folding and export of proteins and hydrolysis of unfolded proteins are disbalanced in the endoplasmic reticulum (ER) of cancer cells, leading to so-called ER stress. Agents further augmenting this effect are used as anticancer drugs including clinically approved proteasome inhibitors bortezomib and carfilzomib. However, these drugs can affect normal cells, which also rely strongly on ER functions, leading, for example, to accumulation of reactive oxygen species (ROS). To address this problem, we have developed ER-targeted prodrugs activated only in cancer cells in the presence of elevated ROS amounts. These compounds are conjugates of cholic acid with N-alkylaminoferrocene-based prodrugs. We confirmed their accumulation in the ER of cancer cells, their anticancer efficacy, and cancer cell specificity. These prodrugs induce ER stress, attenuate mitochondrial membrane potential, and generate mitochondrial ROS leading to cell death via necrosis. We also demonstrated that the new prodrugs are activated in vivo in Nemeth-Kellner lymphoma (NK/Ly) murine model.
CRIS-Team WoS Importer:2021-04-16

Anticancer Aminoferrocene Derivatives Inducing Production of Mitochondrial Reactive Oxygen Species - Özkan, Hülya Gizem; Thakor, Vanrajsinh; Xu, Honggui; Bila, Galyna; Bilyy, Rostyslav; Bida, Daria; Boettcher, Martin; Mougiakakos, Dimitrios; Tietze, Rainer; Mokhir, Andriy (Chemistry - A European Journal, 2022)
Elevated levels of reactive oxygen species (ROS) and deficient mitochondria are two weak points of cancer cells. Their simultaneous targeting is a valid therapeutic strategy to design highly potent anticancer drugs. The remaining challenge is to limit the drug effects to cancer cells without affecting normal ones. We have previously developed three aminoferrocene (AF)-based derivatives, which are activated in the presence of elevated levels of ROS present in cancer cells with formation of electron-rich compounds able to generate ROS and reduce mitochondrial membrane potential (MMP). All of them exhibit important drawbacks including either low efficacy or high unspecific toxicity that prevents their application in vivo up to date. Herein we describe unusual AF-derivatives lacking these drawbacks. These compounds act via an alternative mechanism: they are chemically stable in the presence of ROS, generate mitochondrial ROS in cancer cells, but not normal cells and exhibit anticancer effect in vivo.
CRIS-Team WoS Importer:2022-04-29

Anticancer Effect of an Electronically Coupled Oligoferrocene - Zeh, Gina; Haines, Philipp; Miehlich, Matthias; Kienz, Torben; Neidlinger, Andreas; Friedrich, Ralf P.; Alexiou, Christoph; Hampel, Frank; Guldi, Dirk Michael; Meyer, Karsten; Schatz, Jürgen; Heinze, Katja; et al. (Organometallics, 2020)
The mode of anticancer activity of simple ferrocenes often relies on their intracellular oxidation with the formation of cytotoxic ferrocenium species. The former compounds should be considered as prodrugs and derived from them ferroceniums as drugs. The drugs are 17e- organometallic species. Therefore, they are chemically unstable and decompose with formation of free cyclopentadienyl ligands (which are further transformed to more stable species) and iron ions. The short lifetime of ferrocenium drugs limits the anticancer effect of ferrocene prodrugs. In this paper we prepared a series of acylated aminoferrocene monomers, dimers, and higher oligonuclear complexes FcN (where N = 1-4). Drugs [FcN]+ derived from FcN (N > 1) are more stable than monomeric [Fc]+, provided that the ferrocene units are electronically coupled. Correspondingly, we expected that FcN species will be more potent anticancer agents in comparison to the related monomers. These assumptions were confirmed for dimer 10. We observed that this prodrug has sufficient solubility in aqueous solution (100 μM) and favorable lipophilicity (log P = 2.2 ± 0.2). Ferrocene units in 10 are efficiently electronically coupled via a -C(═O)NH- linker according to cyclic voltammetry, differential pulse voltammetry, and spectroelectrochemistry. We observed that 10 is the most efficient catalyst of the production of reactive oxygen species (ROS) and the most active anticancer agent in comparison to control monomers and their mixtures.
CRIS-Team Scopus Importer:2020-09-14

A nucleic acid dependent chemical photocatalysis in live human cells - Arian, Dumitru; Clo, Emiliano; Gothelf, Kurt V.; Mokhir, Andriy (Chemistry - A European Journal, 2010)
Only two nucleic acid directed chemical reactions that are compatible with live cells have been reported to date. Neither of these processes generate toxic species from nontoxic starting materials. Reactions of the latter type could be applied as gene-specific drugs, for example, in the treatment of cancer. We report here the first example of a chemical reaction that generates a cytotoxic drug from a nontoxic prodrug in the presence of a specific endogeneous ribonucleic acid in live mammalian cells. In this case, the pro-drug is triplet oxygen and the drug is singlet oxygen. The key component of this reaction is an inert molecule (InP-2′-OMe-RNA/Q-2′-OMe-RNA; P: photosensitizer; Q: quencher), which becomes an active photosensitizer (InP-2′-OMe-RNA) in the presence of single-stranded nucleic acid targets. Upon irradiation with red light, the photosensitizer produces over 6000 equivalents of toxic singlet oxygen per nucleic acid target. This reaction is highly sequence specific. To detect the generation of singlet oxygen in live cells, we prepared a membrane-permeable and water-soluble fluorescent scavenger, a derivative of 2,5-diphenylisobenzofurane. The scavenger decomposes upon reaction with singlet oxygen and this is manifested in a decrease in the fluorescence intensity. This effect can be conveniently monitored by flow cytometry. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA.

A nucleic acid-directed, red light-induced chemical reaction - Fueloep, Annabelle; Peng, Xiaohua; Greenberg, Marc M.; Mokhir, Andriy (Chemical Communications, 2010)
The first nucleic acid-directed catalytic photochemical reaction that is induced by nontoxic red light was developed. This reaction is fast, high yielding, sequence specific, and enables one to functionalize an oligonucleotide. © 2010 The Royal Society of Chemistry.

A prodrug of 3-(ferrocenylaminocarbonyloxymethyl)phenol activated by reactive oxygen species in cancer cells - Özkan, Hülya Gizem; Mokhir, Andriy (Journal of Inorganic Biochemistry, 2022)
Hybrid drugs containing ferrocene and phenol residues, whose π systems are not conjugated with each other, exhibit potent anticancer activity as previously reported. Few important open questions are remaining before practical application of these drugs becomes possible. First, their mode of action is not fully clarified. Second, it is not known whether these drugs exhibit cancer cell specificity. Third, due to the presence of the phenol moiety, these drugs can potentially be oxidatively deactivated and eliminated via phase II metabolism when applied in vivo. In this paper we report on synthesis of three prodrugs of aminoferrocene-phenol hybrids, where the phenolic OH group is masked as a boronic acid pinacol ester. We confirmed that the best prodrug in this small series p5 is activated in human ovarian cancer A2780 and Burkitt's lypmphoma BL-2 cells, but remains inactive in representative normal SBLF9 cells. Since p5 does not contain free phenolic OH groups, it will not be metabolized as phenols in vivo. We confirmed that the mechanism of anticancer activity of aminoferrocene-phenol prodrug p5 relies on generation of reactive oxygen species in cells.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Aminoferrocene; Anticancer; Mitochondria; Phenol; Prodrug; Reactive oxygen species

'Caged' peptide nucleic acids activated by red light in a singlet oxygen mediated process - Koenig, Sandra G.; Mokhir, Andriy (Bioorganic & Medicinal Chemistry Letters, 2013)
Common 'caged' nucleic acid binders, which can be applied for temporal and spatial control of gene expression, are activated by high energy light (<450 nm). The light of this type is damaging to cells and is strongly absorbed by cellular components. Therefore, shifting the triggering light to the visible region (>550 nm) is highly desirable. Herein we report on a cyclic peptide nucleic acid (PNA), whose backbone contains a 9,10-dialkoxy-substituted anthracene linker. The sequence of this compound was selected to be complementary to a representative microRNA (miR-92). We demonstrated that the cyclic PNA does not bind complementary nucleic acids and is, correspondingly, 'caged'. Its uncaging can be conducted by its exposure to red light (635 nm) in the presence of pyropheophorbide-a. The latter process is mediated by singlet oxygen (O), which cleaves the 9,10-dialcoxyanthracene linker within the PNA with formation of a linear PNA, an efficient binder of the complementary ribonucleic acid. This is the first example of a red light-activated, 'caged' peptide nucleic acid. © 2013 Elsevier Ltd. All rights reserved.

Chemical design of the heterodifunctionalized iron(II) clathrochelates with terminal biorelevant carboxyl group and reactive triple C≡C bond: Synthesis, structure, redox properties and their stability in various media - Selin, Roman A.; Chornenka, Nina V.; Chernii, Viktor Ya; Mokhir, Andriy; Vologzhanina, Anna V.; Belov, Alexander S.; Pomadchik, Alexander L.; Voloshin, Y. Z. (Inorganica Chimica Acta, 2019)
The heterodifunctionalized iron(II) clathrochelates, the molecules of which contain the terminal biorelevant carboxyl and reactive triple C≡C groups were obtained using the two-step synthetic procedures by a subsequent substitution of their dichloroclathrochelate precursor with para-carboxyphenylthiolate anion and 2-propargylamine. The complexes obtained were characterized using elemental analysis, HR-APPI and MALDI-TOF mass spectrometries, UV–Vis, 1H, 13C1H, 11B and 19F NMR spectroscopies, and by the single crystal X-ray diffraction for an iron(II) monochloroclathrochelate with terminal propargylamine group. Its FeN6-coordination polyhedron possesses a distorted trigonal prismatic – trigonal-antiprismatic geometry with the average distortion angle φ of approximately 26.1°. Fe–N distances in this monoribbed-functionalized molecule vary in a narrow range from 1.883(3) to 1.901(4) Å and the height h of the above polyhedron is equal to 2.30 Å. Cyclic voltammograms study of these complexes contain the single cathodic wave assigned to the metal-centered processes of the cathodic Fe2+/+ reduction and anodic Fe+/2+ re-oxidation, thus suggesting their quasi-reversible character. Chemical reactions (including a complete decomposition and a reductive hydrodehalogenation of the macrobicyclic molecules) of the propargylamine and propargylamide iron(II) clathrochelates was studied in various media and under the different experimental conditions using TLC, high-resolution APPI mass, NMR and UV–vis spectra, suggesting a complete slow destruction of the macrobicyclic frameworks of their molecules in aqueous solutions (including those modeling the physiological conditions).
CRIS-Team Scopus Importer:2019-08-16
Keywords: Chemical stability; Clathrochelates; Cyclic voltammetry; Iron complexes; Ligand reactivity; Macrocyclic compounds

Chemical Tools for Targeted Amplification of Reactive Oxygen Species in Neutrophils - Reshetnikov, Viktor; Hahn, Jonas; Maueroeder, Christian; Czegley, Christine; Munoz, Luis Enrique; Herrmann, Martin; Hoffmann, Markus; Mokhir, Andriy (Frontiers in Immunology, 2018)
A number of chemical compounds are known, which amplify the availability of reactive oxygen species (ROS) in neutrophils both in vitro and in vivo. They can be roughly classified into NADPH oxidase 2 (NOX2)-dependent and NOX2-independent reagents. NOX2 activation is triggered by protein kinase C agonists (e.g., phorbol esters, transition metal ions), redox mediators (e.g., paraquat) or formyl peptide receptor (FPR) agonists (e.g., aromatic hydrazine derivatives). NOX2-independent mechanisms are realized by reagents affecting glutathione homeostasis (e.g., L-buthionine sulfoximine), modulators of the mitochondrial respiratory chain (e.g., ionophores, inositol mimics, and agonists of peroxisome proliferator-activated receptor gamma) and chemical ROS amplifiers [e.g., aminoferrocene-based prodrugs (ABPs)]. Since a number of inflammatory and autoimmune diseases, as well as cancer and bacterial infections, are triggered or enhanced by aberrant ROS production in neutrophils, it is tempting to use ROS amplifiers as drugs for the treatment of these diseases. However, since the known reagents are not cell specific, their application for treatment likely causes systemic enhancement of oxidative stress, leading to severe side effects. Cell-targeted ROS enhancement can be achieved either by using conjugates of ROS amplifiers with ligands binding to receptors expressed on neutrophils (e.g., the GPI-anchored myeloid differentiation marker Ly6G or FPR) or by designing reagents activated by neutrophil function [e.g., phagocytic activity or enzymatic activity of neutrophil elastase (NE)]. Since binding of an artificial ligand to a receptor may trigger or inhibit priming of neutrophils the latter approach has a smaller potential for severe side effects and is probably better suitable for therapy. Here, we review current approaches for the use of ROS amplifiers and discuss their applicability for treatment. As an example, we suggest a possible design of neutrophil-specific ROS amplifiers, which are based on NE-activated ABPs.
EVALuna2:213257

COMBinatorial Oligo FISH: directed labeling of specific genome domains in differentially fixed cell material and live cells. - Schmitt, Eberhard; Schwarz-Finsterle, Jutta; Stein, Stefan; Boxler, Carmen; Mueller, Patrick; Mokhir, Andriy; Kraemer, Roland; Cremer, Christoph; Hausmann, Michael (Methods in Molecular Biology, 2010)
With the improvement and completeness of genome databases, it has become possible to develop a novel fluorescence in situ hybridization (FISH) technique called COMBinatorial Oligo FISH (COMBO-FISH). In contrast to other (standard) FISH applications, COMBO-FISH makes use of a bioinformatic approach for probe set design. By means of computer genome database search, oligonucleotide stretches of typical lengths of 15-30 nucleotides are selected in such a way that they all colocalize within a given genome (gene) target. Typically, probe sets of about 20-40 stretches are designed within 50-250 kb, which is enough to get an increased fluorescence signal specifically highlighting the target from the background. Although "specific colocalization" is the only necessary condition for probe selection, i.e. the probes of different lengths can be composed of purines and pyrimidines, we additionally refined the design strategy restricting the probe sets to homopurine or homopyrimidine oligonucleotides so that depending on the probe orientation either double (requiring denaturation of the target double strand) or triple (omitting denaturation of the target strand) strand bonding of the probes is possible. The probes used for the protocols described below are DNA or PNA oligonucleotides, which can be synthesized by established automatized techniques. We describe different protocols that were successfully applied to label gene targets via double- or triple-strand bonding in fixed lymphocyte cell cultures, bone marrow smears, and formalin-fixed, paraffin-wax embedded tissue sections. In addition, we present a procedure of probe microinjection in living cells resulting in specific labeling when microscopically detected after fixation.

Control of the photocatalytic activity of bimetallic complexes of pyropheophorbide- A by nucleic acids - Arian, Dumitru; Kovbasyuk, Larisa; Mokhir, Andriy (Inorganic Chemistry, 2011)
Photocatalytic activity of a photosensitizer (PS) in an oligodeoxyribonucleotide duplex 5′-PS∼ODN1/ODN2∼Q-3′ is inhibited because of close proximity of a quencher Q. The ODN2 in this duplex is selected to be longer than the ODN1. Therefore, in the presence of a nucleic acid (analyte), which is fully complementary to the ODN2 strand, the duplex is decomposed with formation of an analyte/ODN2∼Q duplex and a catalytically active, single stranded PS∼ODN1. In this way the catalytic activity of the PS can be controlled by the specific nucleic acids. We applied this reaction earlier for the amplified detection of ribonucleic acids in live cells (Arian, D.; Cló, E.; Gothelf, K.; Mokhir, A. Chem.-Eur. J.2010, 16(1), 288). As a photosensitizer (PS) we used In (pyropheophorbide-a)chloride and as a quencher (Q) - Black-Hole-Quencher-3 (BHQ-3). The In complex is a highly active photocatalyst in aqueous solution. However, it can coordinate additional ligands containing thiols (e.g., proteins, peptides, and aminoacids), that modulate properties of the complex itself and of the corresponding bio- molecules. These possible interactions can lead to undesired side effects of nucleic acid controlled photocatalysts (PS∼ODN1/ODN2∼Q) in live cells. In this work we explored the possibility to substitute the In complex for those ones of divalent metal ions, Zn and Pd , which exhibit lower or no tendency to coordinate the fifth ligand. We found that one of the compounds tested (Pd(pyropheophorbide-a) is as potent and as stable photosensitizer as its In analogue, but does not coordinate additional ligands that makes it more suitable for cellular applications. When the Pd complex was introduced in the duplex PS∼ODN1/ODN2∼Q as a PS, its photocatalytic activity could be controlled by nucleic acids as efficiently as that of the corresponding In complex. © 2011 American Chemical Society.

Cyanine- and Rhodamine-Derived Alkynes for the Selective Targeting of Cancerous Mitochondria through Radical Thiol-Yne Coupling in Live Cells - Köckenberger, Johannes; Klemt, Insa; Sauer, Caroline; Arkhypov, Anton; Reshetnikov, Viktor; Mokhir, Andriy; Heinrich, Markus (Chemistry - A European Journal, 2023)
Despite their long history and their synthetic potential underlined by various recent advances, radical thiol-yne coupling reactions have so far only rarely been exploited for the functionalization of biomolecules, and no examples yet exist for their application in live cells - although natural thiols show widespread occurrence therein. By taking advantage of the particular cellular conditions of mitochondria in cancer cells, we have demonstrated that radical thiol-yne coupling represents a powerful reaction principle for the selective targeting of these organelles. Within our studies, fluorescently labeled reactive alkyne probes were investigated, for which the fluorescent moiety was chosen to enable both mitochondria accumulation as well as highly sensitive detection. After preliminary studies under cell-free conditions, the most promising alkyne-dye conjugates were evaluated in various cellular experiments comprising analysis by flow cytometry and microscopy. All in all, these results pave the way for improved future therapeutic strategies relying on live-cell compatibility and selectivity among cellular compartments.
CRIS-Team Scopus Importer:2023-06-30
Keywords: alkynes; mitochondria; radicals; selective targeting; thiols

Cytotoxic and immunogenic Potential of Iron (II) Clathrochelates and Irradiation on Lung Cancer Cell Lines - Becker, Ina; Denzler, M.; Heim, Lisanne; Klemt, Insa; Voloshin, Y. Z.; Selin, R.; Mokhir, Andriy; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Dicarboxyl-terminated iron(ii) clathrochelates as ICD-reporters for globular proteins - Kovalska, Vladyslava B.; Vakarov, Serhii; Losytskyy, Mykhaylo; Kuperman, Marina; Chornenka, Nina; Toporivska, Yuliya; Gumienna-Kontecka, Elzbieta; Voloshin, Yan; Varzatskii, Oleg; Mokhir, Andriy (RSC Advances, 2019)
Cage metal complexes iron(ii) clathrochelates, which are inherently CD silent, were discovered to demonstrate intensive output in induced circular dichroism (ICD) spectra upon their assembly to albumins. With the aim to design clathrochelates as protein-sensitive CD reporters, the approach for the functionalization of one chelate α-dioximate fragment of the clathrochelate framework with two non-equivalent substituents was developed, and constitutional isomers of clathrochelate with two non-equivalent carboxyphenylsulfide groups were synthesized. The interaction of designed iron(ii) clathrochelates and their symmetric homologues with globular proteins (serum albumins, lysozyme, β-lactoglobulin (BLG), trypsin, insulin) was studied by protein fluorescence quenching and CD techniques. A highly-intensive ICD output of the clathrochelates was observed upon their association with albumins and BLG. It was shown that in the presence of BLG, different clathrochelate isomers gave spectra of inverted signs, indicating the stabilization of opposite configurations (Λ or Δ) of the clathrochelate framework in the assembly with this protein. So, we suggest that the isomerism of the terminal carboxy group determined preferable configurations of the clathrochelate framework for the fixation in the protein binding site. MALDI TOF results show the formation of BLG-clathrochelate complex with ratio 1:1. Based on the docking simulations, the binding of the clathrochelate molecule (all isomers) to the main BLG binding site (calyx) in its open conformation is suggested. The above results point that the variation of the ribbed substituents at the clathrochelate framework is an effective tool to achieve the specificity of clathrochelate ICD reporting properties to the target protein.
CRIS-Team Scopus Importer:2019-08-20

Dipeptide-catalysed Michael reaction under physiological conditions: Examination of potential bioorthogonality - Schuster, Florian; Grau, Benedikt; Xu, Huiyi; Mokhir, Andriy; Tsogoeva, Svetlana (Bioorganic & Medicinal Chemistry, 2024)
Reactions for drug synthesis under cell-like conditions or even inside living cells can potentially be used e.g., to minimize toxic side effects, to maximize bioactive compound efficacy and/or to address drug delivery problems. Those reactions should be bioorthogonal to enable the generation of drug-like compounds with sufficiently good yields. In the known bioorthogonal Michael reactions, using thiols and phosphines as nucleophiles (e.g., in C–S and C–P bond formation reactions) is very common. No bioorthogonal Michael addition with a carbon nucleophile is known yet. Therefore, the development of such a reaction might be interesting for future drug discovery research. In this work, the metal-free Michael addition between cyclohexanone and various trans-β-nitrostyrenes (C–C bond formation reaction), catalysed by a dipeptide salt H-Pro-Phe-O-Na+, was investigated for the first time in the presence of glutathione (GSH) and in phosphate-buffered saline (PBS). We demonstrated that with electron-withdrawing substituents on the aromatic ring and in β-position of the trans-β-nitrostyrene yields up to 64% can be obtained under physiological conditions, indicating a potential bioorthogonality of the studied Michael reaction. In addition, the selected Michael products demonstrated activity against human ovarian cancer cells A2780. This study opens up a new vista for forming bioactive compounds via C–C bond formation Michael reactions under physiological (cell-like) conditions.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Anticancer activity; Bioorthogonality; Glutathione; Michael addition; Peptide catalysis; Phosphate-buffered saline

DNA-Dye-Conjugates: Conformations and Spectra of Fluorescence Probes - Beierlein, Frank; Paradas Palomo, Miguel; Sharapa, Dmitry; Zozulia, Oleksii; Mokhir, Andriy; Clark, Timothy (Plos One, 2016)
Extensive molecular-dynamics (MD) simulations have been used to investigate DNA-dye and DNA-photosensitizer conjugates, which act as reactants in templated reactions leading to the generation of fluorescent products in the presence of specific desoxyribonucleic acid sequences (targets). Such reactions are potentially suitable for detecting target nucleic acids in live cells by fluorescence microscopy or flow cytometry. The simulations show how the attached dyes/photosensitizers influence DNA structure and reveal the relative orientations of the chromophores with respect to each other. Our results will help to optimize the reactants for the templated reactions, especially length and structure of the spacers used to link reporter dyes or photosensitizers to the oligonucleotides responsible for target recognition. Furthermore, we demonstrate that the structural ensembles obtained from the simulations can be used to calculate steady-state UV-vis absorption and emission spectra. We also show how important quantities describing the quenching of the reporter dye via fluorescence resonance energy transfer (FRET) can be calculated from the simulation data, and we compare these for different relative chromophore geometries.

Esterification vs. 1,3-Dipolar Cycloaddition Synthetic Approaches for Preparation of the Fluorescently Labelled Iron(II) Clathrochelates - Selin, Roman A.; Chernii, Viktor Ya; Kryvorotenko, Dmytro; Mokhir, Andriy; Voloshin, Yan Z. (Journal Macroheterocycles, 2021)
Two most common synthetic approaches (i.e. the esterification and 1,3-dipolar cycloaddition reactions) to a functionalization of the reactive three-dimensional molecular platforms, allowing to obtain the fluorescently labelled iron(II) clathrochelates and, therefore, to study their localization and accumulation in cancer cells, were compared. Because an esterification approach gave the target complexes in a very low yield, if any, such a functionalization of a known propargylamine iron(II) clathrochelate complex with terminal C C bond as a reactive macrobicyclic precursor by the copper-promoted 1,3-dipolar cycloaddition "click" reaction was also tested. This one-pot synthetic procedure allowed to obtain the cumarin-terminated iron(II) cage complex in a high yield; it was characterized using elemental analysis, ESI-TOF mass, and H-1 and C-13H-1 NMR spectra.
CRIS-Team WoS Importer:2021-06-25

Evaluation of N-alkylaminoferrocenes for in-vivo imaging of reactive oxygen species activity using PET and optical imaging - Toms, Johannes; Maschauer, Simone; Daum, Steffen; Reshetnikov, Viktor; Mokhir, Andriy; Prante, Olaf (JOURNAL OF LABELLED COMPOUNDS & RADIOPHARMACEUTICALS, 2019)
CRIS-Team WoS Importer:2019-06-18

Evidence of protein binding by a nucleopeptide based on a thyminedecorated L-diaminopropanoic acid through CD and In Silico studies - Roviello, Valentina; Musumeci, Domenica; Mokhir, Andriy; Roviello, Giovanni N. (Current Medicinal Chemistry, 2021)
Background: Nucleopeptides are chimeric compounds of biomedical importance carrying DNA nucleobases anchored to peptide backbones with the ascertained capacity to bind nucleic acids. However, their ability to interact with proteins involved in pathologies of social relevance is a feature that still requires investigation. The worrying situation currently observed worldwide for the COVID-19 pandemic urgently requires the research on novel anti-SARSCoV- 2 molecular weapons, whose discovery can be aided by in silico predictive studies. Objective: The aim of this work is to explore by spectroscopic methods novel features of a thymine-bearing nucleopeptide based on L-diaminopropanoic acid, including conformational aspects as well as its ability to bind proteins, starting from bovine serum albumin (BSA) as a model protein. Moreover, in consideration of the importance of targeting viral proteins in the current fight against COVID-19, we evaluated in silico the interaction of the nucleopeptide with some of the most relevant coronavirus protein targets. Methods: First, we investigated via circular dichroism (CD) the conformational behaviour of this thymine-bearing nucleopeptide with temperature: we observed CD spectral changes, particularly passing from 15 to 35 °C. Scanning Electron Microscopy (SEM) analysis of the nucleopeptide was also conducted on nucleopeptide solid samples. Additionally, CD binding and preliminary in silico investigations were performed with BSA as a model protein. Moreover, molecular dockings were run using as targets some of the main SARS-CoV-2 proteins. Results: The temperature-dependent CD behaviour reflected the three-dimensional rearrangement of the nucleopeptide at different temperatures, with higher exposure to the solvent of its chromophores at higher temperatures compared to a more stacked structure at a low temperature. SEM analysis of nucleopeptide samples in the solid-state showed a granular morphology, with a low roughness and some thread structures. Moreover, we found through spectroscopic studies that the modified peptide bound the albumin target by inducing significant changes to the protein secondary structure. Conclusion: CD and preliminary in silico studies suggested that the nucleopeptide bound the BSA protein with high affinity according to different binding modes, as testified by binding energy scores lower than -11 kcal/mol. Interestingly, a predictive study performed on 3CLpro and other SARS-CoV-2 protein targets suggested the potential ability of the nucleopeptide to bind with good affinity the main protease of the virus and other relevant targets, including the RNAdependent RNA polymerase, especially when complexed with RNA, the papain-like protease, and the coronavirus helicase at the nucleic acid binding site.
CRIS-Team Scopus Importer:2021-08-27
Keywords: 3CLpro; CD; Coronavirus infections; COVID-19; Nucleopeptide; Pandemics; Protein binding; RNA-protein complex; SARS-CoV-2; SEM

Expanding manganese(iv) aqueous chemistry: unusually stable water-soluble hexahydrazide clathrochelate complexes - Shylin, Sergii I.; Pogrebetsky, James L.; Husak, Alina O.; Bykov, Dmytro; Mokhir, Andriy; Hampel, Frank; Shova, Sergiu; Ozarowski, Andrew; Gumienna-Kontecka, Elzbieta; Fritsky, Igor O. (Chemical Communications, 2021)
Mn cage complexes are rare, and the ones successfully isolated in the solid state are not stable in water and organic solvents. Herein, we present the first report of mononuclear Mn clathrochelates, in which the encapsulated metal exists in the oxidation state +4. The complexes are extremely stable in the crystalline state and in solutions and show rich redox chemistry.
CRIS-Team WoS Importer:2021-10-15

Far-red pentamethine cyanine dyes as fluorescent probes for the detection of serum albumins - Aristova, D.; Volynets, G.; Chernii, S.; Losytskyy, M.; Balanda, A.; Slominskii, Yu; Mokhir, Andriy; Yarmoluk, S.; Kovalska (Royal Society Open Science, 2020)
Benzothiazole based cyanine dyes with bridged groups in the pentamethine chain were studied as potential far-red fluorescent probes for protein detection. Spectral-luminescent properties were characterized for unbound dyes and in the presence of serum albumins (bovine (BSA), human (HSA), equine (ESA)), and globular proteins (beta -lactoglobulin, ovalbumin). We have observed that the addition of albumins leads to a significant increase in dyes fluorescence intensity. However, the fluorescent response of dyes in the presence of other globular proteins was notably lower. The value of fluorescence quantum yield for dye bearing a sulfonate group complexed with HSA amounted to 42% compared with 0.2% for the free dye. The detection limit of HSA by this dye was greater than 0.004 mg ml(-1) which indicates the high sensitivity of dye to low HSA concentrations. Modelling of structure of the dyes complexes with albumin molecules was performed by molecular docking. According to these data, dyes could bind to up to five sites on the HSA molecule; the most preferable are the haemin-binding site in subdomain IB and the dye-binding site in the pocket between subdomains IA, IIA and IIIA. This work confirms that pentamethine cyanine dyes could be proposed as powerful far-red fluorescent probes applicable for highly sensitive detection of albumins.
CRIS-Team WoS Importer:2020-07-24

Far-red pentamethine cyanine dyes as fluorescent probes for the detection of serum albumins: Probes for detection of serum albumins - Aristova, D.; Volynets, G.; Chernii, S.; Losytskyy, M.; Balanda, A.; Slominskii, Yu; Mokhir, Andriy; Yarmoluk, S.; Kovalska, V. (Royal Society Open Science, 2020)
Benzothiazole based cyanine dyes with bridged groups in the pentamethine chain were studied as potential far-red fluorescent probes for protein detection. Spectral-luminescent properties were characterized for unbound dyes and in the presence of serum albumins (bovine (BSA), human (HSA), equine (ESA)), and globular proteins (β-lactoglobulin, ovalbumin). We have observed that the addition of albumins leads to a significant increase in dyes fluorescence intensity. However, the fluorescent response of dyes in the presence of other globular proteins was notably lower. The value of fluorescence quantum yield for dye bearing a sulfonate group complexed with HSA amounted to 42% compared with 0.2% for the free dye. The detection limit of HSA by this dye was greater than 0.004 mg ml -1 which indicates the high sensitivity of dye to low HSA concentrations. Modelling of structure of the dyes complexes with albumin molecules was performed by molecular docking. According to these data, dyes could bind to up to five sites on the HSA molecule; the most preferable are the haemin-binding site in subdomain IB and the dye-binding site in the pocket between subdomains IA, IIA and IIIA. This work confirms that pentamethine cyanine dyes could be proposed as powerful far-red fluorescent probes applicable for highly sensitive detection of albumins.
CRIS-Team Scopus Importer:2020-11-06
Keywords: far-red fluorescent probes; globular proteins; molecular docking; pentamethine cyanine dyes; serum albumins

Fluorescein-labeled derivative for study of cytotoxicity mechanism of iron (II) clathrochelates - Selin, R.; Klemt, Insa; Chernii, V.; Kovalska, V.; Mokhir, Andriy (FEBS OPEN BIO, 2021)
CRIS-Team WoS Importer:2021-08-06

Fluorogenic, catalytic, photochemical reaction for amplified detection of nucleic acids - Dutta, Subrata; Fülöp, Annabelle; Mokhir, Andriy (Bioconjugate Chemistry, 2013)
Photochemical, nucleic acid-induced reactions, which are controlled by nontoxic red light, are well-suited for detection of nucleic acids in live cells, since they do not require any additives and can be spatially and temporally regulated. We have recently described the first reaction of this type, in which a phenylselenyl derivative of thymidine (5′-PhSeT-ODNa) is cleaved in the presence of singlet oxygen (Fülöp, A., Peng, X., Greenberg, M. M., Mokhir, A. (2010) A nucleic acid directed, red light-induced chemical reaction. Chem. Commun. 46, 5659-5661). The latter reagent is produced upon exposure of a photosensitizer 3′-PS-ODNb (PS = Indium(III)- pyropheophorbide-a-chloride: InPPa) to >630 nm light. In 2012 we reported on a fluorogenic version of this reaction (Dutta, S., Flottmann, B., Heilemann, M., Mokhir, A. (2012) Hybridization and reaction-based, fluorogenic nucleic acid probes. Chem. Commun. 47, 9664-9666), which is potentially applicable for the detection of nucleic acids in cells. Unfortunately, its yield does not exceed 25% and no catalytic turnover could be observed in the presence of substrate excess. This problem occurs due to the efficient, competing oxidation of the substrate containing an electron rich carbon-carbon double bonds (SCH=CHS) in the presence of singlet oxygen with formation of a noncleavable product (SCH=CHSO). Herein we describe a related, but substantially improved photochemical, catalytic transformation of a fluorogenic, organic substrate, which consists of 9,10-dialkoxyanthracene linked to fluorescein, with formation of a bright fluorescent dye. In highly dilute solution this reaction occurs only in the presence of a nucleic acid template. We developed three types of such a reaction and demonstrated that they are high yielding and generate over 7.7 catalytic turnovers, are sensitive to single mismatches in nucleic acid targets, and can be applied for determination of both the amount of nucleic acids and potentially their localization. © 2013 American Chemical Society.

Hybridization and reaction-based fluorogenic nucleic acid probes - Dutta, Subrata; Flottmann, Benjamin; Heilemann, Mike; Mokhir, Andriy (Chemical Communications, 2012)
We developed fluorogenic probes, which are photoactivated in the presence of specific nucleic acid templates with the release of fluorescent dyes. This templated reaction can be used to target specific nucleic acids in complex mixtures. We further demonstrate that this reaction can be monitored by single-molecule fluorescence imaging. © 2012 The Royal Society of Chemistry.

Hybrids of a 9-anthracenyl moiety and fluorescein as chemodosimeters for the detection of singlet oxygen in live cells - Chercheja, Serghei; Daum, Steffen; Xu, Honggui; Beierlein, Frank; Mokhir, Andriy (Organic & Biomolecular Chemistry, 2019)
Singlet oxygen (1O2) plays an important role in human innate immune response, plant physiology and anticancer photodynamic therapy (PDT). Therefore, its monitoring by convenient and sensitive methods (e.g. by detecting a fluorescence signal) by using non-toxic reagents would be advantageous. Known fluorogenic 1O2-chemodosimeters can potentially consume reducing agents in cells leading to the generation of toxic side products that limit their applications. In this paper we report on a series of 9-anthracenyl-fluorescein hybrids, which do not require any reducing agents for their reaction with 1O2. The selected compound 8d at a very low concentration of 100 nM is able to detect 1O2 in live human promyelocytic leukemia HL-60 cells with over 35-fold fluorescence signal enhancement within only 20 min assay time. This chemodosimeter is not toxic to HL-60 cells at concentrations ≤1 μM (higher concentrations were not tested) even at long incubation times ≤48 h.
CRIS-Team Scopus Importer:2019-12-10

Identification of Boronic Acid Derivatives as an Active Form of N-Alkylaminoferrocene-Based Anticancer Prodrugs and Their Radiolabeling with 18F - Daum, Steffen; Toms, Johannes; Reshetnikov, Viktor; Özkan, Hülya; Hampel, Frank; Maschauer, Simone; Hakimioun, Amir Hossein; Beierlein, Frank; Sellner, Leopold; Schmitt, Michael; Prante, Olaf; Mokhir, Andriy (Bioconjugate Chemistry, 2019)
N-Alkylaminoferrocene (NAAF)-based prodrugs are activated in the presence of elevated amounts of reactive oxygen species (ROS), which corresponds to cancer specific conditions, with formation of NAAF and p-quinone methide. Both products act synergistically by increasing oxidative stress in cancer cells that causes their death. Though it has already been demonstrated that the best prodrugs of this type retain their antitumor activity in vivo, the effects were found to be substantially weaker than those observed in cell cultures. Moreover, the mechanistic studies of these compounds in vivo are missing. For clarification of these important questions, labeling of the prodrugs with radioactive moieties would be necessary. In this paper, we first observed that the representative NAAF-based prodrugs are hydrolyzed in dilute aqueous solutions to the corresponding arylboronic acids. We confirmed that these products are responsible for ROS amplification and anticancer properties of the parent prodrugs. Next, we developed the efficient synthetic protocol for radiolabeling the hydrolyzed NAAF-based prodrugs by [18F]fluoroglucosylation under the conditions of the copper(I)-catalyzed azide–alkyne 1,3-dipolar cycloaddition and used this protocol to prepare one representative hydrolyzed NAAF-based prodrug radiolabeled with 18F. Finally, we studied the stability of the 18F-labeled compound in human serum in vitro and in rat blood in vivo and obtained preliminary data on its biodistribution in vivo in mice carrying pancreatic (AR42J) and prostate (PC3) tumors by applying PET imaging studies. The compound described in this paper will help to understand in vivo effects (e.g., pharmacokinetics, accumulation in organs, the nature of side effects) of these prodrugs that will strongly contribute to their advancement to clinical trial

Immunophanotype modulating Properties of Ferrous Clathrochelates and Irradiation in Lung Cancer Cells - Alomo, Jannik; Becker, I.; Roessel, T.; Denzler, M.; Heim, L.; Mokhir, Andriy; Klemt, Insa; Voloshin, Y.; Selin, R.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

In Silico Study of Camptothecin-Based Pro-Drugs Binding to Human Carboxylesterase 2 - Beierlein, Frank; Horn, Anselm; Sticht, Heinrich; Mokhir, Andriy; Imhof, Petra (Biomolecules, 2024)
Pro-drugs, which ideally release their active compound only at the site of action, i.e., in a cancer cell, are a promising approach towards an increased specificity and hence reduced side effects in chemotherapy. A popular form of pro-drugs is esters, which are activated upon their hydrolysis. Since carboxylesterases that catalyse such a hydrolysis reaction are also abundant in normal tissue, it is of great interest whether a putative pro-drug is a probable substrate of such an enzyme and hence bears the danger of being activated not just in the target environment, i.e., in cancer cells. In this work, we study the binding mode of carboxylesters of the drug molecule camptothecin, which is an inhibitor of topoisomerase I, of varying size to human carboxylesterase 2 (HCE2) by molecular docking and molecular dynamics simulations. A comparison to irinotecan, known to be a substrate of HCE2, shows that all three pro-drugs analysed in this work can bind to the HCE2 protein, but not in a pose that is well suited for subsequent hydrolysis. Our data suggest, moreover, that for the irinotecan substrate, a reactant-competent pose is stabilised once the initial proton transfer from the putative nucleophile Ser202 to the His431 of the catalytic triad has already occurred. Our simulation work also shows that it is important to go beyond the static models obtained from molecular docking and include the flexibility of enzyme–ligand complexes in solvents and at a finite temperature. Under such conditions, the pro-drugs studied in this work are unlikely to be hydrolysed by the HCE2 enzyme, indicating a low risk of undesired drug release in normal tissue.
CRIS-Team Scopus Importer:2024-03-08
Keywords: camptothecin; docking; homology model; human carboxylesterase; molecular dynamics simulations; pro-drug

Intracellular amplifiers of reactive oxygen species affecting mitochondria as radiosensitizers - Xu, Honggui; Reshetnikov, Viktor; Wondrak, Marit; Eckhardt, Lisa; Kunz-Schughart, Leoni A.; Janko, Christina; Tietze, Rainer; Alexiou, Christoph; Borchardt, Hannes; Aigner, Achim; Gong, Wenjie; Schmitt, Michael; et al. (Cancers, 2022)
Radiotherapy (RT) efficacy can be improved by using radiosensitizers, i.e., drugs enhancing the effect of ionizing radiation (IR). One of the side effects of RT includes damage of normal tissue in close proximity to the treated tumor. This problem can be solved by applying cancer specific radiosensitizers. N-Alkylaminoferrocene-based (NAAF) prodrugs produce reactive oxygen species (ROS) in cancer cells, but not in normal cells. Therefore, they can potentially act as cancer specific radiosensitizers. However, early NAAF prodrugs did not exhibit this property. Since functional mitochondria are important for RT resistance, we assumed that NAAF prodrugs affecting mitochondria in parallel with increasing intracellular ROS can potentially exhibit synergy with RT. We applied sequential Cu+-catalyzed alkyne-azide cycloadditions (CuAAC) to obtain a series of NAAF derivatives with the goal of improving anticancer efficacies over already existing com-pounds. One of the obtained prodrugs (2c) exhibited high anticancer activity with IC50 values in the range of 5–7.1 µM in human ovarian carcinoma, Burkitt’s lymphoma, pancreatic carcinoma and T-cell leukemia cells retained moderate water solubility and showed cancer specificity. 2c strongly affects mitochondria of cancer cells, leading to the amplification of mitochondrial and total ROS production and thus causing cell death via necrosis and apoptosis. We observed that 2c acts as a radiosensitizer in human head and neck squamous carcinoma cells. This is the first demonstration of a synergy between the radiotherapy and NAAF-based ROS amplifiers.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Cancer; Mitochondrion; N-alkylaminoferrocene; Prodrug; Radiotherapy; Reactive oxygen species

Iron vs. cobalt clathrochelate electrocatalysts of HER: The first example on a cage iron complex - Dolganov, Alexander V.; Belov, Alexander S.; Novikov, Valentin V.; Vologzhanina, Anna V.; Mokhir, Andriy; Bubnov, Yurii N.; Voloshin, Yan Z. (Dalton Transactions, 2013)
New macrobicyclic 2-thiopheneboron-capped iron and cobalt(ii) tris-dioximates showed high electrocatalytic activity for hydrogen production from H ions. This is the first example of the hydrogen evolution reaction electrocatalyzed by a clathrochelate iron complex, which catalyzes the hydrogen production at low overpotential. © The Royal Society of Chemistry 2013.

Lysosome-targeting amplifiers of reactive oxygen species as anticancer prodrugs - Daum, Steffen; Reshetnikov, Viktor; Sisa, Miroslav; Dumych, Tetyana; Lootsik, Maxim D.; Bilyy, Rostyslav; Bila, Evgenia; Janko, Christina; Alexiou, Christoph; Herrmann, Martin; Sellner, Leopold; Mokhir, Andriy (Angewandte Chemie-International Edition, 2017)
Cancer cells produce elevated amounts of reactive oxygen species that has been used to design cancer specific prodrugs. Their activation relies on at least a bimolecular process, where a prodrug reacts with ROS. However, at low µM concentrations of the prodrugs and ROS the activation is usually inefficient. Herein we suggested and validated a potentially general approach for solving this intrinsic problem of ROS-dependent prodrugs. In particular, known 4-(N-ferrocenyl-N-benzylaminocarbonyloxymethyl)phenylboronic acid pinacol ester was converted to its lysosome specific analogue. Since lysosomes contain the higher concentration of active ROS than cytoplasm, activation of the latter prodrug was facilitated with respect to the parent compound. In particular, it was found to exhibit high anticancer activity in a variety of cancer cell lines (IC50 3.5-7.2 µM) and in vivo (40 mg/kg, NK/Ly murine model), but remained weakly toxic towards non-malignant cells (IC50 15-30 µM).
EVALuna2:13450

Metal complex derivatives of peptide nucleic acids (PNA). - Kraemer, Roland; Mokhir, Andriy (Metal ions in life sciences, 2012)
Peptide nucleic acid (PNA) is a non-cyclic pseudopeptide-nucleic acid structural mimic with promising applications within diagnostics and drug discovery. This review focuses on metal complex derivatives of PNA. Metal ions and their complexes display unique physical and chemical properties and offer the opportunity to introduce new labels and probes for bioanalytical and diagnostic applications of PNA, but also to modulate or to introduce new (for example catalytic) functions and biological activities.

Mitochondria-Catalyzed Activation of Anticancer Prodrugs - Raucheisen, Michael; Attia, Dina; Körber, Marlies; Crevillén, Alejandra Aroca; Hidalgo, Andrés; Beierlein, Frank; Imhof, Petra; Mokhir, Andriy (ChemCatChem, 2025)
Mitochondria mediate electron transport chain (ETC) to power ATP synthase. In cancer cells, the ETC is disturbed leading to leakage of electrons that ultimately results in generation of H2O2. This difference between cancer and healthy cells can be used for the design of cancer-specific prodrugs as confirmed in several proof-of-concept studies. Unfortunately, the known prodrugs are either insufficiently cancer cell specific or their activation efficacy is low. In this work, we solved this problem by optimizing the conjugate of a drug camptothecin and a H2O2-responsive aminoferrocene to obtain the prodrug C. The multistep reaction of the prodrug C with H2O2 is >20-fold more efficient than that of the parent system. The prodrug is accumulated and activated in mitochondria of cancer cells in a H2O2-dependent fashion. The anticancer efficacy towards human ovarian cancer A2780 and monocytic leukemia THP1 cells is improved from 573 and >3000 nM (for prodrug B) to 142 and 479 nM (for prodrug C) correspondingly. Additionally to the excellent activity, the new prodrug is not toxic in vivo to a range of blood (red and white blood cells, neutrophils, monocytes, platelets) and bone marrow cells (monocytes, B and T cells and others) in contrast to camptothecin.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Aminoferrocene; Anticancer; Catalysis; Mitochondria; Reactive oxygen species

Monomethine cyanine probes for visualization of cellular RNA by fluorescence microscopy - Aristova, Daria; Kosach, Viktoriia; Chernii, Svitlana; Slominsky, Yuriy; Balanda, Anatoliy; Filonenko, Valeriy; Yarmoluk, Sergiy; Rotaru, Alexandru; Özkan, Hülya; Mokhir, Andriy; Kovalska, Vladyslava B. (Methods and Applications in Fluorescence, 2021)
We have studied spectral-luminescent properties of the monomethine cyanine dyes both in their free states and in the presence of either double-stranded deoxyribonucleic acids (dsDNAs) or single-stranded ribonucleic acids (RNAs). The dyes possess low fluorescence intensity in an unbound state, which is increased up to 479 times in the presence of the nucleic acids. In the presence of RNAs, the fluorescence intensity increase was stronger than that observed in the presence of dsDNA. Next, we have performed staining of live and fixed cells by all prepared dyes. The dyes proved to be cell and nuclear membrane permeant. They are photostable and brightly stain RNA-containing organelles in both live and fixed cells. The colocalization confirmed the specific nucleoli staining with anti-Ki-67 antibodies. The RNA digestion experiment has confirmed the selectivity of the dyes toward intracellular RNA. Based on the obtained results, we can conclude that the investigated monomethine cyanine dyes are useful fluorescent probes for the visualization of intracellular RNA and RNA-containing organelles such as nucleoli by using fluorescence microscopy.
CRIS-Team WoS Importer:2021-07-30

N-Alkylaminoferrocene-Based Prodrugs Targeting Mitochondria of Cancer Cells - Reshetnikov, Viktor; Özkan, Hülya; Daum, Steffen; Janko, Christina; Alexiou, Christoph; Sauer, Caroline; Heinrich, Markus; Mokhir, Andriy (Molecules, 2020)
Intracellular concentration of reactive oxygen species (e.g., H2O2) in cancer cells is elevated over 10-fold as compared to normal cells. This feature has been used by us and several other research groups to design cancer specific prodrugs, for example, N-alkylaminoferrocene (NAAF)-based prodrugs. Further improvement of the efficacy of these prodrugs can be achieved by their targeting to intracellular organelles containing elevated reactive oxygen species (ROS) amounts. For example, we have previously demonstrated that lysosome-targeted NAAF-prodrugs exhibit higher anticancer activity in cell cultures, in primary cells and in vivo (Angew. Chem. Int. Ed. 2017, 56, 15545). Mitochondrion is an organelle, where electrons can leak from the respiratory chain. These electrons can combine with O2, generating O2-• that is followed by dismutation with the formation of H2O2. Thus, ROS can be generated in excess in mitochondria and targeting of ROS-sensitive prodrugs to these organelles could be a sensible possibility for enhancing their efficacy. We have previously reported on NAAF-prodrugs, which after their activation in cells, are accumulated in mitochondria (Angew. Chem. Int. Ed. 2018, 57, 11943). Now we prepared two hybrid NAAF-prodrugs directly accumulated in mitochondria and activated in these organelles. We studied their anticancer activity and mode of action. Based on these data, we concluded that ROS produced by mitochondria is not available in sufficient quantities for activation of the ROS-responsive prodrugs. The reason for this can be efficient scavenging of ROS by antioxidants. Our data are important for the understanding of the mechanism of action of ROS-activatable prodrugs and will facilitate their further development.
CRIS-Team Scopus Importer:2020-06-16
Keywords: cancer; mitochondrion; N-alkylaminoferrocene; prodrug; reactive oxygen species

N-alkyl functionalized squaraine dyes as fluorescent probes for the detection of serum albumins - Syniugina, A. T.; Chernii, S. V.; Losytskyy, M. Yu; Özkan, Hülya; Slominskii, Yu L.; Syniugin, A. R.; Pekhnyo, V. I.; Mokhir, Andriy; Yarmoluk, S. M. (Biopolymers and Cell, 2022)
Aim. Here we synthesize a series of benzoindolium squaraine dyes with N-substituents (SQ) and examine these dyes as fluorescent probes to detect serum albumins. Methods. Organic synthesis, fluorescent spectroscopy, absorption spectroscopy, fluorescent microscopy. Results. The spectral-luminescent properties of SQ dyes in the aqueous solution were investigated in the presence of bovine serum albumin (BSA), human serum albumin (HSA), equine serum albumin (ESA), ovalbumin (OVA), beta-lactoglobulin (BLG) and lysozyme (LYS), as well as in the presence of nucleic acid. The maxima of excitation spectra of the studied dyes in the buffer solution ranged within 623–673 nm, with the fluorescence emission maxima lying between 635 and 690 nm. All these dyes showed a similar increase in the fluorescence intensity with serum albumins and at the same time with the red shift up to 12 nm, which could point out the binding of the dyes to proteins. These dyes demonstrate a noticeably lower fluorescence intensity in the presence of OVA, BLG, and LYS, which structurally differ from serum albumins. The studied dyes gave no significant fluorescent response to the addition of nucleic acids. The equilibrium constants of dyes binding to BSA (K) were estimated as 3.0 ± 0.3x105 M-1 for SL-2411 and 2.4 ± 0.6x105 M-1 for SL-2412. Based on the relative values of K, we could suppose that the mechanism of dye-BSA binding is the interaction of the chromophore of the dye with the protein globule. It was shown that SL-2411 penetrates the cell membrane and distributes in the cytoplasm without co-localization with MitoTracker Green. Conclusion. These dyes could apply fluorescent spectroscopy for protein detection and potentially visualize cell components with minimum to no autofluorescence.
CRIS-Team Scopus Importer:2024-12-16
Keywords: absorptions spec-troscopy; fluorescence microscopy; fluorescent detection; fluorescent spectroscopy; serum albumins; squaraine dyes

NOX2 mediates quiescent handling of dead cell remnants in phagocytes - Hahn, Jonas; Euler, Maximilien; Kilgus, Emelie; Kienhöfer, Deborah; Stoof, Julia; Knopf, Jasmin; Hahn, Madelaine; Harrer, Thomas; Hultqvist, Malin; Olofsson, Peter; Mokhir, Andriy; Holmdahl, Rikard; et al. (Redox Biology, 2019)
The phagocyte NADPH oxidase (the NOX2 complex) generates superoxide, the precursor to reactive oxygen species (ROS). ROS possess both antimicrobial and immunoregulatory function. Inactivating mutations in alleles of the NOX2 complex cause chronic granulomatous disease (CGD), characterized by an enhanced susceptibility to infections and autoimmune diseases such as Systemic lupus erythematosus (SLE). The latter is characterized by insufficient removal of dead cells, resulting in an autoimmune response against components of the cell's nucleus when non-cleared apoptotic cells lose their membrane integrity and present autoantigenic molecules in an inflammatory context. Here we aimed to shed light on the role of the NOX2 complex in handling of secondary necrotic cells (SNECs) and associated consequences for inflammation and autoimmunity during lupus. We show that individuals with SLE and CGD display accumulation of SNECs in blood monocytes and neutrophils. In a CGD phenotypic mouse strain (Ncf1** mice) build-up of SNECs in Ly6CHI blood monocytes was connected with a delayed degradation of the phagosomal cargo and accompanied by production of inflammatory mediators. Treatment with H2O2 or activators of ROS-formation reconstituted phagosomal abundance of SNECs to normal levels. Induction of experimental lupus further induced increased antibody-dependent uptake of SNECs into neutrophils. Lupus-primed Ncf1** neutrophils took up more SNECs than wild type neutrophils, whereas SNEC-accumulation in regulatory Ly6C−/LO monocytes was lower in Ncf1**mice. We deduce that the inflammatory rerouting of immune-stimulatory necrotic material into inflammatory phagocyte subsets contributes to the connection between low ROS production by the NOX2 complex and SLE.
CRIS-Team Scopus Importer:2019-08-06

Nucleic acid-specific photoactivation of oligodeoxyribonucleotides labeled with deuterated dihydro-N, N, N′, N′-tetramethylrhodamine using green light - Schikora, Margot; Dutta, Subrata; Mokhir, Andriy (Histochemistry and Cell Biology, 2014)
We developed a simple protocol for high-yielding synthesis of conjugates of a deuterated dihydro-N, N, N′, N′-tetramethylrhodamine (F*) with oligodeoxyribonucleotides and a 2′-OMe RNA (a representative nuclease-resistant, chemically modified oligonucleotide) using easily accessible starting materials including NaBD and conjugates of oligonucleotides with N, N, N′, N′-tetramethylrhodamine (F). These compounds were found to be stable in air and insensitive to light at 525, 635 and 650 nm, whereas slow activation occurs upon their exposure to 470 nm light. However, at the conditions of the templated reaction, in the presence of a target nucleic acid and a photocatalyst based on the eosin structure, the F* is oxidized forming fluorescent F. This reaction is >30-fold faster than the background reaction in the absence of the template. Moreover, the presence of a single mismatch in the target nucleic acid slows down the templated reaction by eightfold. These activatable dyes can potentially find applications as nucleic acid-specific probes for super-resolution imaging in live cells. © 2014 Springer-Verlag Berlin Heidelberg.

Part 2: In vitro cytotoxicity studies of two ML 2 complexes (M = Pd, Pt; L = 2-cyano-2-isonitroso-N-morpholylacetamide, HMCO - Ratcliff, Jessica; Durham, Paul; Keck, Michael; Mokhir, Andriy; Gerasimchuk, Nikolay (Inorganica Chimica Acta, 2012)
In recent years, many non-classical groups of Pt-compounds, including complexes with the trans-geometry, polynuclear complexes, and compounds with a variety of extended heterocyclic ligands, were obtained and studied. Part 1 of this work contains the results of our X-ray crystallographic and computational studies of a group of recently-discovered cytotoxic Pd and Pt complexes of the new cyanoxime ligands HPipCO and HMCO. Here we present the results of our in vitro investigations of two M(MCO) (M = Pd, Pt) compounds against two morphologically different human cancer cell lines - epithelial cervical cancer HeLa cells, and WiDr solid tumor colon carcinoma. The Trypan Blue exclusion method was used for the assessment of the complexes' cytotoxicity. The data indicated a profound in vitro activity of new M(MCO) (M = Pd, Pt) complexes, comparable to that of cisplatin, which was used as a positive control. The palladium MCO complex was found to be consistently slightly more active than its corresponding Pt-analog. Binding of the above compounds to a variety of the DNA was studied by UV-Vis spectroscopy, gel electrophoresis, fluorescent intercalator displacement (FID) assay, and the mitochondria metabolism assay. No evidence of an interaction of either Pd(MCO) or Pt(MCO) complex with different types of DNA was found, which infers a mechanism of cytotoxicity of these new metallo-cyanoximates different from one of the cisplatin family. This immediately suggests different active species involved in the cellular interactions, as well as different metabolites. Consequently, it implies the absence of the negative side effects so common to the cisplatin family of anticancer drugs. © 2011 Elsevier B.V. All rights reserved.

Plasmid-DNA Delivery by Covalently Functionalized PEI-SPIONs as a Potential ‘Magnetofection’ Agent - Stein, René; Pfister, Felix; Friedrich, Bernhard; Blersch, Pascal-Raphael; Unterweger, Harald; Arkhypov, Anton; Mokhir, Andriy; Kolot, Mikhail; Alexiou, Christoph; Tietze, Rainer (Molecules, 2022)
Nanoformulations for delivering nucleotides into cells as vaccinations as well as treatment of various diseases have recently gained great attention. Applying such formulations for a local treatment strategy, e.g., for cancer therapy, is still a challenge, for which improved delivery concepts are needed. Hence, this work focuses on the synthesis of superparamagnetic iron oxide nanoparticles (SPIONs) for a prospective “magnetofection” application. By functionalizing SPIONs with an active catechol ester (CafPFP), polyethyleneimine (PEI) was covalently bound to their surface while preserving the desired nanosized particle properties with a hydrodynamic size of 86 nm. When complexed with plasmid-DNA (pDNA) up to a weight ratio of 2.5% pDNA/Fe, no significant changes in particle properties were observed, while 95% of the added pDNA was strongly bound to the SPION surface. The transfection in A375-M cells for 48 h with low amounts (10 ng) of pDNA, which carried a green fluorescent protein (GFP) sequence, resulted in a transfection efficiency of 3.5%. This value was found to be almost 3× higher compared to Lipofectamine (1.2%) for such low pDNA amounts. The pDNA-SPION system did not show cytotoxic effects on cells for the tested particle concentrations and incubation times. Through the possibility of additional covalent functionalization of the SPION surface as well as the PEI layer, Caf-PEI-SPIONs might be a promising candidate as a magnetofection agent in future.
CRIS-Team Scopus Importer:2022-11-25
Keywords: cytotoxicity; ligand exchange; magnetofection; pentafluorophenyl ester; plasmid-DNA; superparamagnetic iron oxide nanoparticles (SPIONs); surface functionalization; transfection

Radiosynthesis of an 18 F-fluoroglycosylated aminoferrocene for in-vivo imaging of reactive oxygen species activity by PET - Toms, Johannes; Reshetnikov, Viktor; Maschauer, Simone; Mokhir, Andriy; Prante, Olaf (Journal of Labelled Compounds & Radiopharmaceuticals, 2018)
The imaging of reactive oxygen species (ROS) at the molecular level with high sensitivity and specificity by positron emission tomography (PET) could be of enormous interest to increase our knowledge about ROS activity and signalling, especially in tumours. The aim of this research was to optimise the click chemistry-based radiosynthesis of an 18 F-labelled aminoferrocene glycoconjugate that was derived from an N-alkylaminoferrocene lead structure known to have anticancer activity in vitro. Applying the solvent system phosphate buffer/THF (12/5), Cu(OAc)2 and sodium ascorbate as reducing agent at 60°C, the alkyne 1 reacted with the 18 F-labelled glycosyl azide [18 F]2 in the presence of carrier 3 (47μM) to obtain carrier-added [18 F]4 in a radiochemical yield of 85%. Interestingly, the addition of carrier was essential for sufficient radiochemical yield, because it suppressed the oxidation of no-carrier-added (n.c.a.) [18 F]4. Future work will include the formulation of c.a. [18 F]4 for studying its biodistribution in tumour-bearing mice.
EVALuna2:212380

Reactive oxygen species-responsive RNA interference - Rühle, Jennifer; Klemt, Insa; Abakumova, Tatiana; Sergeeva, Olga; Vetosheva, Polina; Zatsepin, Timofei; Mokhir, Andriy (Chemical Communications, 2022)
Due to oxidative instability, arylboronic acids are not compatible with the solid-phase synthesis of nucleic acids. We solved this problem and, based on these findings, developed siRNA prodrugs activated in the presence of reactive oxygen species (ROS) in vivo. These prodrugs can be used for specific targeting of ROS-rich cancer cells.
CRIS-Team WoS Importer:2022-04-01

Red Fluorescent Aminoferrocene (Pro)Drugs for in Cellulo and in Vivo Imaging - Chernii, Svitlana; Selin, Roman; Bila, Galyna; Bilyy, Rostyslav; Körber, Marlies; Mokhir, Andriy (Chemistry - A European Journal, 2024)
Red fluorescent dyes are usually charged, lipophilic molecules with relatively high molecular weight, which tend to localize in specific intracellular locations, e. g., a cyanine dye Cy5 is biased towards mitochondria. They are often used as markers of biomolecules including nucleic acids and proteins. Since the molecular weight of the dyes is much smaller than that of the biomolecules, the labelling has a negligible effect on the properties of the biomolecules. In contrast, conjugation of the dyes to low molecular weight (pro)drugs can dramatically alter their properties. For example, conjugates of Cy5 with lysosome-targeting aminoferrocenes accumulate in mitochondria and exhibit no intracellular effects characteristic for the parent (pro)drugs. Herein we tested several neutral and negatively charged dyes for labelling lysosome-targeting aminoferrocenes 7 and 8 as well as a non-targeted control 3. We found that a BODIPY derivative BDP-TR exhibits the desired unbiased properties: the conjugation does not disturb the intracellular localization of the (pro)drugs, their mode of action, and cancer cell specificity. We used the conjugates to clarify the mechanism of action of the aminoferrocenes. In particular, we identified new intermediates, explained why lysosome-targeting aminoferrocenes are more potent than their non-targeted counterparts, and evaluated their distribution in vivo.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Cancer; Drug; Imaging; Prodrug; Red fluorescent dye

Red Light Triggered Fluorogenic Reaction with Picomolar Sensitivity Toward Nucleic Acids - Zozulia, Oleksii; Bachmann, Tobias; Mokhir, Andriy (Bioconjugate Chemistry, 2019)
We have previously reported on a red light triggered, singlet oxygen-mediated fluorogenic reaction that is templated in a highly sequence specific fashion by nucleic acids (S. Dutta, A. Fulop, A. Mokhir, Bioconjgate Chem.2013, 24 (9), 1533-1542). Up to the present date, it has remained a single templated reaction responsive to nontoxic >650 nm light. However, it is operative only in the presence of relatively high (>2 nM) concentrations of templates that dramatically limit its applicability in nucleic acid detection. In the current work, we established that an inefficient intermolecular electron transfer involved in reduction of the 1,4-endoperoxide intermediate, formed in the rate-limiting reaction step, is responsible for inhibition of the reaction at low reagent concentrations. We suggested the solution of the problem which includes a combination of a cleavable (9-alkoxyanthracene) moiety with a two-electron donating fragment in one molecule. This approach enables the efficient intramolecular electron transfer to the endoperoxide intermediate in the critical reaction step. Due to the intramolecular character of the latter process, it is practically independent of concentration of the reagents. The reaction based on the improved cleavable moiety was found to be >200-fold more sensitive than the previously reported one. It is fast, sequence specific, and compatible with live cells. Accounting for short reactions times (<30 min), nontoxic trigger (red light), excellent sensitivity, and sequence specificity, this is presently the best reported photochemical templated reaction compatible with live cells.
CRIS-Team Scopus Importer:2019-08-09

Red light-triggered nucleic acid-templated reaction based on cyclic oligonucleotide substrates - Zozulia, Oleksii; Bachmann, Tobias; Deussner-Helfmann, Nina S.; Beierlein, Frank; Heilemann, Mike; Mokhir, Andriy (Chemical Communications, 2019)
A red light-triggered reaction based on cyclic oligonucleotide substrates that is accelerated over 30-fold by specific nucleic acid templates and generates a bright fluorescent probe was developed. We confirmed that this reaction is compatible with fluorescence correlation spectroscopy (FCS) thereby allowing detection of nucleic acids down to 1 nM.
CRIS-Team Scopus Importer:2019-09-17

Red light-triggered photoreduction on a nucleic acid template - Dutta, Subrata; Rühle, Jennifer; Schikora, Margot; Deussner-Helfmann, Nina S.; Heilemann, Mike; Zatsepin, Timofei; Duchstein, Patrick; Zahn, Dirk; Knoer, Guenther; Mokhir, Andriy (Chemical Communications, 2020)
Conjugate Sn(iv)(pyropheophorbide a)dichloride-(peptide nucleic acid) catalyzes reduction of azobenzene derivatives in the presence of complementary nucleic acid (NA) upon irridiation with red light (660 nm). This is the first red light-induced NA-templated photoreduction. It is highly sensitive to single mismatches in the NA-template and can detect down to 5 nM NAs.
CRIS-Team Scopus Importer:2020-09-11

Regular high-nuclearity species from square building blocks: A triangular 3 × [2 × 2] Ni 12 complex generated by the self-assembly of three [2 × 2] Ni 4 molecular grids - Moroz, Yurii S.; Demeshko, Serhiy; Haukka, Matti; Mokhir, Andriy; Mitra, Utpal; Stocker, Michael; Müller, Paul; Meyer, Franc; Fritsky, Igor O. (Inorganic Chemistry, 2012)
A dodecanuclear 3 × [2 × 2] nickel(II) complex has been obtained via the self-association of three tetranuclear [2 × 2] molecular grids. X-ray diffraction shows a "propeller-like" structure of the [Ni ] scaffold with a central μ -hydroxide. The dodecanuclear species remains stable in solution and can be deposited without decomposition on highly ordered pyrolytic graphite surfaces. © 2012 American Chemical Society.

ROS-Responsive N-Alkylaminoferrocenes for Cancer-Cell-Specific Targeting of Mitochondria - Reshetnikov, Viktor; Daum, Steffen; Janko, Christina; Karawacka, Weronika; Tietze, Rainer; Alexiou, Christoph; Paryzhak, Solomiya; Dumych, Tetiana; Bilyy, Rostyslav; Tripal, Philipp; Schmid, Benjamin; Palmisano, Ralf; et al. (Angewandte Chemie International Edition, 2018)
Mitochondrial membrane potential is more negative in cancer cells than in normal cells, allowing cancer targeting by delocalized lipophilic cations (DLCs). However, as the difference is rather small, these drugs affect also normal cells. Now a concept of pro-DLCs is proposed based on an N-alkylaminoferrocene structure. These prodrugs are activated by the reaction with reactive oxygen species (ROS) forming ferrocenium-based DLCs. Since ROS are overproduced in cancer, the high-efficiency cancer-cell-specific targeting of mitochondria could be achieved as demonstrated by fluorescence microscopy in combination with two fluorogenic pro-DLCs in vitro and in vivo. We prepared a conjugate of another pro-DLC with a clinically approved drug carboplatin and confirmed that its accumulation in mitochondria was higher than that of the free drug. This was reflected in the substantially higher anticancer effect of the conjugate.
EVALuna2:35451

Selective dsDNA-templated formation of copper nanoparticles in solution - Rotaru, Alexandru; Dutta, Subrata; Jentzsch, Elmar; Gothelf, Kurt; Mokhir, Andriy (Angewandte Chemie International Edition, 2010)
chemical equation presented A helping strand: A method to selectively form copper nanoparticles in solution using double-stranded DNA has been developed. The size of the nanoparticles is controlled by the length of the dsDNA template, and single-stranded DNA did not act as a template (see scheme). Single-stranded overhangs in dsDNA were used to prepare a nanostructure in which two metallized dsDNA segments were linked together by a nonmetallized rigid linker. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Self-assembly cavitand precisely recognizing hexafluorosilicate: A concerted action of two coordination and twelve CH⋯F bonds - Degtyarenko, Anna S.; Rusanov, Eduard B.; Bauza, Antonio; Frontera, Antonio; Krautscheid, Harald; Chernega, Alexander N.; Mokhir, Andriy; Domasevitch, Konstantin V. (Chemical Communications, 2013)
Bis-pyridazine tectons support the structure of metallosupramolecular cavitand CuL, which is capable of selective encapsulation of SiF anions by a set of multiple host-guest interactions. © 2013 The Royal Society of Chemistry.

Short, terminally modified 2′-OMe RNAs as inhibitors of microRNA - Blechinger, Jenny; Pieper, Hanna; Marzenell, Paul; Kovbasyuk, Larisa A.; Serva, Andrius; Starkuviene, Vytaute; Erfle, Holger; Mokhir, Andriy (Chemical Communications, 2013)
We applied 14-mer 2′-OMe RNAs as inhibitors of selected micro RNAs. To improve their properties, we introduced a trimethoxystilbene residue at the 5′-terminus and three 2′-fluoro-2′-deoxynucleotides at the 3′-terminus to obtain potent inhibitors, whose mismatch discrimination is substantially better than that of typically applied >18-mers. © 2013 The Royal Society of Chemistry.

Single molecule atomic force microscopy studies of photosensitized singlet oxygen behavior on a DNA origami template - Helmig, Sarah; Rotaru, Alexandru; Arian, Dumitru; Kovbasyuk, Larisa; Arnbjerg, Jacob; Ogilby, Peter R.; Kjems, Jorgen; Mokhir, Andriy; Besenbacher, Flemming; Gothelf, Kurt V. (Acs Nano, 2010)
DNA origami, the folding of a long single-stranded DNA sequence (scaffold strand) by hundreds of short synthetic oligonucleotides (staple strands) into parallel aligned helices, is a highly efficient method to form advanced self-assembled DNA-architectures. Since molecules and various materials can be conjugated to each of the short staple strands, the origami method offers a unique possibility of arranging molecules and materials in well-defined positions on a structured surface. Here we combine the action of light with AFM and DNA nanostructures to study the production of singlet oxygen from a single photosensitizer molecule conjugated to a selected DNA origami staple strand on an origami structure. We demonstrate a distance-dependent oxidation of organic moieties incorporated in specific positions on DNA origami by singlet oxygen produced from a single photosensitizer located at the center of each origami. © 2010 American Chemical Society.

Single-molecule chemical reactions on DNA origami. - Voigt, Niels V.; Torring, Thomas; Rotaru, Alexandru; Jacobsen, Mikkel F.; Ravnsbaek, Jens B.; Subramani, Ramesh; Mamdouh, Wael; Kjems, Jorgen; Mokhir, Andriy; Besenbacher, Flemming; Gothelf, Kurt Vesterager (Nature nanotechnology, 2010)
DNA nanotechnology and particularly DNA origami, in which long, single-stranded DNA molecules are folded into predetermined shapes, can be used to form complex self-assembled nanostructures. Although DNA itself has limited chemical, optical or electronic functionality, DNA nanostructures can serve as templates for building materials with new functional properties. Relatively large nanocomponents such as nanoparticles and biomolecules can also be integrated into DNA nanostructures and imaged. Here, we show that chemical reactions with single molecules can be performed and imaged at a local position on a DNA origami scaffold by atomic force microscopy. The high yields and chemoselectivities of successive cleavage and bond-forming reactions observed in these experiments demonstrate the feasibility of post-assembly chemical modification of DNA nanostructures and their potential use as locally addressable solid supports.

SPIONs functionalized with small peptides for binding of lipopolysaccharide, a pathophysiologically relevant microbial product. - Karawacka, Weronika; Janko, Christina; Unterweger, Harald; Mühlberger, Marina; Lyer, Stefan; Taccardi, Nicola; Mokhir, Andriy; Jira, Wolfgang; Peukert, Wolfgang; Boccaccini, Aldo R.; Kolot, Mikhail; Strauss, Richard; et al. (Colloids and Surfaces B-Biointerfaces, 2018)
Systemic inflammation such as sepsis represents an acute life-threatening condition, to which often no timely remedy can be found. A promising strategy may be to functionalize magnetic nanoparticles with specific peptides, derived from the binding motives of agglutinating salivary proteins, that allow immobilization of pathogens. In this work, superparamagnetic iron oxide nanoparticles with stable polycondensed aminoalkylsilane layer were developed, to which the heterobifunctional linkers N-succinimidyl 3-(2-pyridyldithio)-propanoate (SDPD) and N-succinimidyl bromoacetate (SBA) were bound. These linkers were further chemoselectively reacted with the thiol group of singularly present cysteines of selected peptides. The resulting functional nanoparticles underwent a detailed physicochemical characterization. The biocompatibility of the primarily coated aminoalkylsilane particles was also investigated. To test the pathogen-binding efficacy of the particles, the lipopolysaccharide-immobilization capacity of the peptide-coated particles was compared with free peptides. Here, one particle-bound peptide species succeeded in capturing 90% of the toxin, whereas the degree of immobilization of the toxin with a system that varied in the sequence of the peptide dropped to 35%. With these promising results, we hope to develop extracorporeal magnetic clearance systems for removing pathogens from the human body in order to accelerate diagnosis and alleviate acute disease conditions such as sepsis.

Study of anti-fibrillogenic activity of iron(II) clathrochelates - Kovalska, Vladyslava B.; Losytskyy, Mykhaylo Yu.; Varzatskii, Oleg A.; Cherepanov, Vsevolod V.; Voloshin, Yan Z.; Mokhir, Andriy; Yarmoluk, Sergiy M.; Volkov, Sergiy V. (Bioorganic & medicinal chemistry, 2014)
The macrocyclic compounds mono- and bis-iron(II) clathrochelates were firstly studied as potential anti-fibrillogenic agents using fluorescent inhibitory assay, atomic force microscopy and flow cytometry. It is shown that presence of the clathrochelates leads to the change in kinetics of insulin fibrillization reaction and reduces the amount of formed fibrils (up to 70%). The nature of ribbed substituent could determine the activity of clathrochelates - the higher inhibitory effect is observed for compounds containing carboxybenzenesulfide groups, while the inhibitory properties only slightly depend on the size of complex species. The mono- and bis-clathrochelate derivatives of meta-mercaptobenzoic acid have close values of IC namely 16 ± 2 and 24 ± 5 μM, respectively. The presence of clathrochelates decreases the fibril diameter from 5-12 nm for free insulin fibrils to 3-8 nm for these formed in the clathrochelate presence, it also prevents the lateral aggregation of mature fibrils and formation of superfibrillar clusters. However the addition of clathrochelate results in more heterogeneous (both by size and structure) insulin aggregates population as compared to the free insulin. This way, cage complexes - iron(II) clathrochelates are proposed as efficient agents able to suppress the protein aggregation processes. © 2014 Elsevier Ltd. All rights reserved.

Supramolecular Recognition of Cytidine Phosphate in Nucleotides and RNA Sequences - Morozov, Boris; Oshchepkov, Aleksandr S.; Klemt, Insa; Agafontsev, Aleksandr; Krishna, Swathi; Hampel, Frank; Xu, Honggui; Mokhir, Andriy; Guldi, Dirk Michael; Kataev, Evgeny (JACS Au, 2022)
Supramolecular recognition of nucleotides would enable manipulating crucial biochemical pathways like transcription and translation directly and with high precision. Therefore, it offers great promise in medicinal applications, not least in treating cancer or viral infections. This work presents a universal supramolecular approach to target nucleoside phosphates in nucleotides and RNA. The artificial active site in new receptors simultaneously realizes several binding and sensing mechanisms: encapsulation of a nucleobase via dispersion and hydrogen bonding interactions, recognition of the phosphate residue, and a self-reporting feature─“turn-on” fluorescence. Key to the high selectivity is the conscious separation of phosphate- and nucleobase-binding sites by introducing specific spacers in the receptor structure. We have tuned the spacers to achieve high binding affinity and selectivity for cytidine 5′ triphosphate coupled to a record 60-fold fluorescence enhancement. The resulting structures are also the first functional models of poly(rC)-binding protein coordinating specifically to C-rich RNA oligomers, e.g., the 5′-AUCCC(C/U) sequence present in poliovirus type 1 and the human transcriptome. The receptors bind to RNA in human ovarian cells A2780, causing strong cytotoxicity at 800 nM. The performance, self-reporting property, and tunability of our approach open up a promising and unique avenue for sequence-specific RNA binding in cells by using low-molecular-weight artificial receptors.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cytosine; encapsulation; fluorescence sensing; nucleotide recognition; synthetic receptors

Synthesis and characterization of an Fe(I) cage complex with high stability towards strong H-acids - Voloshin, Yan Z.; Novikov, Valentin V.; Nelyubina, Yulia; Belov, Alexander S.; Roitershtein, Dmitrii M.; Savitsky, Anton; Mokhir, Andriy; Sutter, Jörg; Miehlich, Matthias; Meyer, Karsten (Chemical Communications, 2018)

Synthesis and nucleic acid binding evaluation of a thyminyl L-diaminobutanoic acid-based nucleopeptide - Musumeci, Domenica; Mokhir, Andriy; Roviello, Giovanni N. (Bioorganic Chemistry, 2020)
Herein we present the synthesis of a L-diaminobutanoic acid (DABA)-based nucleopeptide (3), with an oligocationic backbone, realized by solid phase peptide synthesis using thymine-bearing DABA moieties alternating in the sequence with free ones. CD studies evidenced the ability of this oligothymine nucleopeptide, well soluble in aqueous solution, to alter the secondary structure particularly of complementary RNA (poly rA vs poly rU) and inosine-rich RNAs, like poly rI and poly rIC, and showed its preference in binding double vs single-stranded DNAs. Furthermore, ESI mass spectrometry revealed that 3 bound also G-quadruplex (G4) DNAs, with either parallel or antiparallel topologies (adopted in our experimental conditions by c-myc and tel22, respectively). However, it caused detectable changes only in the CD of c-myc (whose parallel G4 structure was also thermally stabilized by 3 °C), while leaving unaltered the antiparallel structure of tel22. Interestingly, CD and UV analyses suggested that 3 induced a hybrid mixed parallel/antiparallel G4 DNA structure in a random-coil tel22 DNA obtained under salt-free buffer conditions. Titration of the random-coil telomeric DNA with 3 gave quantitative information on the stoichiometry of the obtained complex. Overall, the findings of this work suggest that DABA-based nucleopeptides are synthetic nucleic acid analogues potentially useful in antigene and antisense strategies. Nevertheless, the hexathymine DABA-nucleopeptide shows an interesting behaviour as molecular tool per se thanks to its efficacy in provoking G4 induction in random coil G-rich DNA, as well as for the possibility to bind and stabilize c-myc oncogene in a G4 structure.
CRIS-Team Scopus Importer:2020-05-22
Keywords: C-myc; Diaminobutanoic acid; DNA quadruplex; Nucleopeptide; Prebiotic; RNA binding; Synthesis; Telomeric DNA

Synthesis and photophysical properties of indolenine styrylcyanine dye and its carboxyl-labeled derivative - Chernii, Svitlana; Selin, Roman A.; Tretyakova, Iryna; Dovbiy, Yan; Pekhnyo, Vasyl; Rotaru, Alexandru; Chernii, Viktor; Kovalska, Vladyslava B.; Mokhir, Andriy (Biointerface Research in Applied Chemistry, 2023)
The indolenine styrylcyanine dye and its carboxyl-labeled derivative were synthesized using condensation of the corresponding indolenines with 4-(dimethylamino) benzaldehyde in the presence of an alkaline catalyst. The spectral-luminescent properties of studied dyes in organic solvents, the aqueous solution (pH 7.9), and the presence of different biomacromolecules were investigated. The functionalization of the dye structure by the carboxylic group led to a bathochromic shift of fluorescence emission spectra while having no impact on dye specificity. It is established that studied styrylcyanines exhibited no or low preference towards biomacromolecules and no accumulation at a specific site within cells.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Absorption; Flow cytometry; Fluorescence microscopy; Fluorescence spectroscopy; Indolenine styrylcyanine dye

Synthesis and spectral characterization of the first fluorescein-tagged iron(ii) clathrochelates, their supramolecular interactions with globular proteins, and cellular uptake - Selin, Roman A.; Klemt, Insa; Chernii, Viktor Ya; Losytskyy, Mykhaylo Yu; Chernii, Svitlana; Mular, Andrzej; Gumienna-Kontecka, Elzbieta; Kovalska, Vladyslava B.; Voloshin, Yan Z.; Vologzhanina, Anna V.; Dorovatovskii, Pavel V.; Mokhir, Andriy (RSC Advances, 2021)
A fluorescein-tagged iron(ii) cage complex was obtained in a moderate total yield using a two-step synthetic procedure starting from its propargylamine-containing clathrochelate precursor. An 11-fold decrease in fluorescence quantum yield is observed in passing from the given fluorescein-based dye to its clathrochelate derivative. An excitation energy transfer from the terminal fluorescent group of the macrobicyclic molecule to its quasiaromatic highly π-conjugated clathrochelate framework can explain this effect. The kinetics of the hydrolysis of the acetyl groups of acetylated fluorescein azide and its clathrochelate derivative in the presence of one equivalent of BSA evidenced no strong supramolecular host-guest interactions between BSA and the tested compounds. Study of a chemical stability of the deacetylated iron(ii) clathrochelate suggested the formation of a supramolecular 1:1 BSA-clathrochelate assembly. Moreover, an addition of BSA or HSA to its solution caused the appearance of strong clathrochelate-based ICD outputs. The fluorescence emission anisotropy studies also evidenced the supramolecular binding of the fluorescein-tagged iron(ii) clathrochelate to the BSA macromolecule, leading to a high increase in this type of anisotropy. Subcellular uptake of the fluorescein-tagged molecules was visualized using fluorescence microscopy and showed its distribution to be mainly in the cytosol without entering the nucleus or accumulating in any other organelle. An X-rayed crystal of the above propargylamide macrobicyclic precursor with a reactive terminal CC bond contains the clathrochelate molecules of two types,AandB. The encapsulated iron(ii) ion in these molecules is situated in the center of its FeN6-coordination polyhedron, the geometry of which is intermediate between a trigonal prism (TP) and a trigonal antiprism (TAP). The Fe-N distances vary from 1.8754(6) to 1.9286(4) Å and the heightshof their distorted TP-TAP polyhedra are very similar (2.30 and 2.31 Å); their values ofφare equal to 25.3 and 26.6°. In this crystal, the molecules of typesAandBparticipate in different types of hydrogen bonding, giving H-bonded clathrochelate tetramers through their carboxylic and amide groups, respectively; these tetramers are connected to H-bonded chains.
CRIS-Team Scopus Importer:2021-03-19

The Influence of Iron(II) Clathrochelates and Irradiation on Cell Death, reactive Oxygen Radicals, and Danger Signals in the human SK-MES1 Lung Cancer Cell Line - Roessel, T.; Becker, I.; Alomo, Jannik; Denzler, M.; Heim, L.; Klemt, Insa; Voloshin, Y.; Selin, R.; Mokhir, Andriy; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Triggering RNA Interference by Photoreduction under Red Light Irradiation - Rühle, Jennifer; Klemt, Insa; Mokhir, Andriy (Molecules, 2023)
RNA interference (RNAi) using small interfering RNAs (siRNAs) is a powerful tool to target any protein of interest and is becoming more suitable for in vivo applications due to recent developments in RNA delivery systems. To exploit RNAi for cancer treatment, it is desirable to increase its selectivity, e.g., by a prodrug approach to activate the siRNAs upon external triggering, e.g., by using light. Red light is especially well suited for in vivo applications due to its low toxicity and higher tissue penetration. Known molecular (not nanoparticle-based) red-light-activatable siRNA prodrugs rely on singlet oxygen (1O2)-mediated chemistry. 1O2 is highly cytotoxic. Additionally, one of the side products in the activation of the known siRNA prodrugs is anthraquinone, which is also toxic. We herein report on an improved redlight-activatable siRNA prodrug, which does not require 1O2 for its activation. In fact, the 5′ terminus of the antisense strand is protected with an electron-rich azobenzene promoiety. It is reduced and cleaved upon red light exposure in the presence of Sn(IV)(pyropheophorbide a)dichloride acting as a catalyst and ascorbate as a bulk reducing agent. We confirmed the prodrug activation upon red light irradiation both in cell-free settings and in human ovarian cancer A2780 cells.
CRIS-Team Scopus Importer:2023-06-09
Keywords: azobenzene; photoreduction; promoiety; red light activation; RNAi; selective cancer targeting; siRNA prodrug

Trimethine Cyanine Dyes as NA-Sensitive Probes for Visualization of Cell Compartments in Fluorescence Microscopy - Aristova, Daria; Selin, Roman A.; Heil, Hannah Sophie; Kosach, Viktoriia; Slominsky, Yuriy; Yarmoluk, Sergiy; Pekhnyo, Vasyl; Kovalska, Vladyslava B.; Henriques, Ricardo; Mokhir, Andriy; Chernii, Svitlana (ACS Omega, 2022)
We propose symmetrical cationic trimethine cyanine dyes with β-substituents in the polymethine chain based on modified benzothiazole and benzoxazole heterocycles as probes for the detection and visualization of live and fixed cells by fluorescence microscopy. The spectral-luminescent properties of trimethine cyanines have been characterized for free dyes and in the presence of nucleic acids (NA) and globular proteins. The studied cyanines are low to moderate fluorescent when free, but in the presence of NA, they show an increase in emission intensity up to 111 times; the most pronounced emission increase was observed for the dyes T-2 in the presence of dsDNA and T-1 with RNA. Spectral methods showed the binding of all dyes to nucleic acids, and different interaction mechanisms have been proposed. The ability to visualize cell components of the studied dyes has been evaluated using different human cell lines (MCF-7, A2780, HeLa, and Hs27). We have shown that all dyes are cell-permeant staining nucleus components, probably RNA-rich nucleoli with background fluorescence in the cytoplasm, except for the dye T-5. The dye T-5 selectively stains some structures in the cytoplasm of MCF-7 and A2780 cells associated with mitochondria or lysosomes. This effect has also been confirmed for the normal type of cell line-human foreskin fibroblasts (Hs27). The costaining of dye T-5 with MitoTracker CMXRos Red demonstrates specificity to mitochondria at a concentration of 0.1 μM. Colocalization analysis has shown signals overlapping of dye T-5 and MitoTracker CMXRos Red (Pearson's Coefficient value = 0.92 ± 0.04). The photostability study shows benzoxazole dyes to be up to ∼7 times more photostable than benzothiazole ones. Moreover, studied benzoxazoles are less cytotoxic at working concentrations than benzothiazoles (67% of cell viability for T-4, T-5 compared to 12% for T-1, and ∼30% for T-2, T-3 after 24 h). Therefore, the benzoxazole T-4 dye is proposed for nucleic acid detection in vitro and intracellular fluorescence imaging of live and fixed cells. In contrast, the benzoxazole dye T-5 is proposed as a good alternative to commercial dyes for mitochondria staining in the green-yellow region of the spectrum.
CRIS-Team Scopus Importer:2022-12-23

Tumor-Specific Reactive Oxygen Species Accelerators Improve Chimeric Antigen Receptor T Cell Therapy in B Cell Malignancies - Yoo, Hyeon Joo; Liu, Yibin; Wang, Lei; Schubert, Maria-Luisa; Hoffmann, Jean-Marc; Wang, Sanmei; Neuber, Brigitte; Hueckelhoven-Krauss, Angela; Gern, Ulrike; Schmitt, Anita; Mueller-Tidow, Carsten; Dreger, Peter; et al. (International Journal of Molecular Sciences, 2019)
Chimeric antigen receptor T cell (CART) therapy is currently one of the most promising treatment approaches in cancer immunotherapy. However, the immunosuppressive nature of the tumor microenvironment, in particular increased reactive oxygen species (ROS) levels, provides considerable limitations. In this study, we aimed to exploit increased ROS levels in the tumor microenvironment with prodrugs of ROS accelerators, which are specifically activated in cancer cells. Upon activation, ROS accelerators induce further generation of ROS. This leads to an accumulation of ROS in tumor cells. We hypothesized that the latter cells will be more susceptible to CARTs. CD19-specific CARTs were generated with a CD19.CAR.CD28.CD137zeta third-generation retroviral vector. Cytotoxicity was determined by chromium-51 release assay. Influence of the ROS accelerators on viability and phenotype of CARTs was determined by flow cytometry. The combination of CARTs with the ROS accelerator PipFcB significantly increased their cytotoxicity in the Burkitt lymphoma cell lines Raji and Daudi, as well as primary chronic lymphocytic leukemia cells. Exposure of CARTs to PipFcB for 48 h did not influence T cell exhaustion, viability, or T cell subpopulations. In summary, the combination of CARTs with ROS accelerators may improve adoptive immunotherapy and help to overcome tumor microenvironment-mediated treatment resistance.
CRIS-Team WoS Importer:2019-06-28

Tuning the structure of aminoferrocene-based anticancer prodrugs to prevent their aggregation in aqueous solution - Daum, Steffen; Babiy, Svetlana; Konovalova, Helen; Hofer, Walter; Shtemenko, Alexander; Shtemenko, Natalia; Janko, Christina; Alexiou, Christoph; Mokhir, Andriy (Journal of Inorganic Biochemistry, 2018)
Aminoferrocene-based prodrugs are activated in cancer cells by reactive oxygen species (ROS). They were shown to exhibit high cytotoxicity towards a variety of cancer cell lines and primary cancer cells, but remain not toxic towards non-malignant cells. However, these prodrugs have rather high lipophilicity leading to relatively low water solubility. In particular, an n-octanol/water partition coefficient for the best aminoferrocene-based pro drug (2) was found to be 4.51 +/- 0.03. Though the approaches for decreasing lipophilicity are straightforward and include the addition of polar residues to the drug structure, these modifications also lead to dramatic decrease of cell permeability and, correspondingly, lower the activity of the drug. Therefore, a delicate balance of polar and unpolar groups should be found to reduce lipophilicity without compromising the useful drug properties. In this study we optimized an N-alkyl substituent, which is a key element responsible for the stabilization of the aminoferrocene drug released in cancer cells from prodrug 2. We found that an N-propargyl residue is an optimal replacement for the N-benzyl fragment. In particular, such a substitution (prodrug 7a) leads to reduction of prodrug lipophilicity down to logP = 3.78 +/- 0.05, improvement of its water solubility, decrease of its propensity towards aggregation and dramatic increase of its ROS-generating properties. Finally, we demonstrated that the optimized prodrug strongly suppresses growth of Guerin's carcinoma (T8) in vivo at the dose of 30 mg/kg.
EVALuna2:213359

Variation of photostability of DNA-sensitive styrylcyanine dyes caused by N-alkyl functionalization - Snihirova, Y. V.; Losytskyy, M. Yu; Kryvorotenko, D. V.; Kuperman, M. V.; Moshynets, O. V.; Yarmoluk, S. M.; Mokhir, Andriy; Kovalska, Vladyslava B. (Biopolymers and Cell, 2020)
Aim. Synthesis and characterization of benzothiazole-based styrylcyanines functionalized by different N-alkyl tail groups as potential photostable probes for nucleic acids (NA) detection. Methods. Chemical synthesis, absorption and fluorescence spectroscopy, irradiation with a visible light source, confocal microscopy. Results. Styrylcyanines are weakly fluorescent when free, but in the presence of NA they show emission intensity increase of up to 83 times; the most pronounced emission increase was observed for the dyes Sbt1 and Sbt3 bearing posi-tively charged N-alkyl tail group. Photostability of the dyes Sbt1 and Sbt3 when non-bound to NA is low while binding to DNA results in a strong increase in their photostability. Dyes with uncharged and negatively charged N-alkyl groups are more photostable when free, and DNA slightly affects their photostability. This is also due to low binding of dyes with negatively charged tail groups to DNA. Sbt1 brightly stains cytoplasm and nuclear components (probably nucleoli) of mesenchymal stem cells; therefore this dye may be used to visualize cytoplasmic RNA and nuclear RNA clusters. Conclusions. Variation of chemical nature of N-alkyl tail group allows to design styrylcyanines of different photostability. Functionalized styrylcyanine dyes may be used for detection of nucleic acids in solution and visualization of RNA-containing components in microscopy.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Fluorescence; Microscopy; NA detection; Photostability; Styrylcyanines

[YIA] AMPLIFICATION OF ROS/NET FORMATION INDUCES RESOLUTION OF INFLAMMATION - Euler, Maximilien; Hahn, Jonas; Herrmann, Martin; Mokhir, Andriy; Hoffmann, Markus (FREE RADICAL BIOLOGY AND MEDICINE, 2022)
CRIS-Team WoS Importer:2022-09-16